Peeling detection label

CN115746724BActive Publication Date: 2026-10-27LINTEC CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202211413355.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2017-08-21
Filing Date
2018-08-09
Publication Date
2026-10-27
Estimated Expiration
2038-08-09

AI Technical Summary

Benefits of technology

[0030]根据本发明,可提供不会在被粘附物上产生残胶的剥离检测标签。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115746724B_ABST
    Figure CN115746724B_ABST
Patent Text Reader

Abstract

The present application relates to a kind of peeling detection labels, it is sequentially stacked and is stacked body, pattern layer and adhesive layer, and satisfy the following requirement (1) of the stacked body, the pattern layer is formed in the surface of the support part, the adhesive layer (X) and substrate layer (Y) at least have, wherein, the elastic modulus of substrate layer (Y) is 10MPa above and 800MPa below.Requirement (1) is when peeling from the adherend after being pasted to the adherend by the above-mentioned peeling detection label, it can be based on the interface peeling between the above-mentioned support and the above-mentioned pattern layer and visually detect whether the above-mentioned peeling detection label is peeled from adherend.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of the application filed on August 9, 2018, with application number 201880053257.X and invention title "Peeling off detection tags". Technical Field

[0002] This invention relates to peel detection labels. Background Technology

[0003] For packaging such as medicines and food, high reliability is required to ensure safety, and tamper-evident labels are used to verify whether the packaging has been opened. Additionally, tamper-evident labels are used for purposes such as preventing unauthorized opening of containers for hazardous materials like medicine bottles and fuel tanks, sealed letters, cosmetic bags, etc., and for preventing the improper use of photographs on identity documents such as passports.

[0004] In addition, tamper-evident labels are used on labels affixed to expensive electronic devices, precision mechanical parts, etc., to prevent tampering with the content displayed on them or to prevent counterfeiting by peeling off the labels of genuine products and affixing them to other products.

[0005] For example, Patent Document 1 discloses an anti-tampering label or sheet, characterized in that it comprises a polystyrene film with a thickness of 10 μm or more and 40 μm or less, and a heat-resistant adhesive layer laminated on one side thereof, wherein the adhesive strength of the heat-resistant adhesive layer as specified in JIS Z 0237 is 15 N / 25 mm or more at 80°C.

[0006] Existing technical documents

[0007] Patent documents

[0008] Patent Document 1: Japanese Patent Application Publication No. 2010-281948 Summary of the Invention

[0009] The problem the invention aims to solve

[0010] Regarding the tamper-evident label or sheet described in Patent Document 1, the polystyrene film breaks when it is attempted to be peeled off, thereby performing the tamper-evident function.

[0011] However, in the existing peel detection labels as described above, there is a problem that the adhered material may become contaminated due to the adhesive layer remaining on the adhered material after a portion of the damaged substrate layer has been left behind.

[0012] The present invention was made in view of the above background, and its object is to provide a peel detection label that does not leave adhesive residue on the adhered object.

[0013] Problem Solving Methods

[0014] The inventors have discovered that the above-mentioned problems can be solved by manufacturing a peel detection label, wherein the peel detection label is a laminate consisting of a support, a pattern layer formed on a portion of the surface of the support, and an adhesive laminate having at least an adhesive layer (X) and a substrate layer (Y), and satisfies specific requirements, wherein the substrate layer (Y) satisfies a specific elastic modulus.

[0015] That is, the present invention relates to the following [1] to

[11] .

[0016] [1] A peel detection label is a laminate formed by sequentially stacking a support, a pattern layer and an adhesive laminate, and satisfying the following requirement (1), wherein the pattern layer is formed on a portion of the surface of the support, and the adhesive laminate has at least an adhesive layer (X) and a substrate layer (Y), wherein the elastic modulus of the substrate layer (Y) is 10 MPa or more and 800 MPa or less.

[0017] Requirement (1): When the peel detection label is pasted onto the adhered object and then peeled off from the adhered object, it is possible to visually detect whether the peel detection label has been peeled off from the adhered object based on the interface peeling that occurs between the support and the pattern layer.

[0018] [2] The peel detection label described in [1] above, wherein the ratio of the thickness (Xt) of the adhesive layer (X) to the thickness (Yt) of the substrate layer (Y) [(Xt) / (Yt)] is 1 / 3 to 3 / 1.

[0019] [3] The peel detection label described in [1] or [2] above, wherein the adhesive laminate is a laminate having an adhesive layer (X) on one surface side of a substrate layer (Y), and the substrate layer (Y) is in contact with the surface of the support and the pattern layer.

[0020] [4] The peel detection label described in [1] or [2] above, wherein the adhesive laminate is a laminate (P1) formed by sequentially stacking a first adhesive layer (X1), a substrate layer (Y) and a second adhesive layer (X2), and the adhesive layer (X1) is in contact with the surface of the support and the pattern layer.

[0021] [5] The peel detection label described in any one of [1] to [4] above, wherein the elastic modulus of the substrate layer (Y) is 600 MPa or less.

[0022] [6] The peel detection label described in any one of [1] to [5] above, wherein the surface of the support body on the side where the pattern layer is formed is a surface treated with pear skin.

[0023] [7] The peel detection label described in [6] above, wherein the pear skin surface treatment is sandblasting.

[0024] [8] The peel detection label described in any one of [1] to [7] above, wherein the pattern layer and the adhesive layer (X) contain resins of the same kind.

[0025] [9] The peel detection label described in [1] to [8] above, wherein the pattern layer is a layer formed of a composition comprising one or more selected from acrylic resins, urethane resins, urethane acrylate resins and polyester resins.

[0026] The adhesive layer (X) is a layer formed from a composition (x) containing an adhesive resin, said adhesive resin comprising one or more selected from acrylic resins, urethane resins, urethane acrylate resins and polyester resins.

[0027]

[10] The peel detection label described in any one of [1] to [9] above, wherein the substrate layer (Y) is a layer formed of a composition (y) comprising a non-adhesive resin (y1), wherein the non-adhesive resin (y1) is selected from one or more of urethane acrylate resins and olefin resins.

[0028]

[11] The peel detection label of any one of [1] to

[10] above, wherein at least one layer selected from the adhesive layer (X) and the substrate layer (Y) is a layer containing a colorant.

[0029] The effects of the invention

[0030] According to the present invention, a peel detection label that does not leave adhesive residue on the adhered object can be provided. Attached Figure Description

[0031] [ Figure 1 The diagram shows a cross-sectional view of a peel detection tag 101, which is an example of the structure of the peel detection tag of the present invention.

[0032] [ Figure 2 The diagram shows a cross-sectional view of a peel detection tag 102, which is an example of the structure of the peel detection tag of the present invention.

[0033] [ Figure 3 The diagram shows a cross-sectional view of a peel detection tag 102, which is an example of the peel detection tag of the present invention, being peeled off from the adhered object 40.

[0034] Symbol Explanation

[0035] 101, 102 Peel off the detection label

[0036] 1. Support

[0037] 2. Pattern layer

[0038] 3. Adhesive layer (X)

[0039] 4. Substrate layer (Y)

[0040] 11 Adhesive laminates

[0041] 12. Adhesive laminate (P1)

[0042] 1a Surface of the support

[0043] 2a Surface of the patterned layer

[0044] 3a Adhesive layer (X) bonding surface

[0045] 4a Surface of substrate layer (Y)

[0046] 12a Adhesive surface of adhesive laminate (P1)

[0047] 31 Adhesive layer (X1)

[0048] 32 Adhesive layers (X2)

[0049] 40 Adhesives

[0050] 50. Gaps created when the peel detection label is peeled off from the adhered material. Detailed Implementation

[0051] In this invention, the determination of whether the resin to be applied is an "adhesive resin" or a "non-adhesive resin" is based on the following steps (1) to (4).

[0052] • Step (1): A 20 μm thick resin layer formed solely from the resin to be tested is placed on a 50 μm thick polyethylene terephthalate (PET) film, and test pieces are cut to a size of 300 mm in length and 25 mm in width.

[0053] • Step (2): In an environment of 23°C and 50% RH (relative humidity), the surface of the test piece with the exposed resin layer is attached to a stainless steel plate (SUS304 360 grinding) and left to stand in the same environment for 24 hours.

[0054] • Step (3): After standing, the adhesive force is determined by the 180° peel method and the stretching speed of 300 mm / min in an environment of 23°C and 50% RH (relative humidity) based on JIS Z0237:2000.

[0055] • Step (4): When the measured adhesive force is 0.1 N / 25 mm or more, the resin to be used is judged as "adhesive resin". On the other hand, when the measured adhesive force is less than 0.1 N / 25 mm, the resin to be used is judged as "non-adhesive resin".

[0056] In this invention, "active ingredient" refers to the component other than the diluent solvent among the components contained in the composition to which the object is made.

[0057] Furthermore, in this invention, "peeling of the peel detection label" refers to, for example, the peeling operation when the adhesive layer (X) of the peel detection label has a peeling material on its adhesive surface, peeling the peel detection label from the peeling material.

[0058] In contrast, in this invention, "re-peeling of the peel detection label" refers to the peeling operation performed when the peel detection label, after the peeling material has been removed, is pasted onto the adhered object and then peeled off from the adhered object.

[0059] In addition, in this invention, "can be visually detected" means that the changes before and after peeling off the detection label can be confirmed by the human eye.

[0060] In this invention, for example, "(meth)acrylic acid" refers to both "acrylic acid" and "methacrylic acid", and so on for other similar terms.

[0061] In addition, the weight-average molecular weight (Mw) is a value determined by gel permeation chromatography (GPC) and converted to standard polystyrene, specifically the value determined based on the method described in the examples.

[0062] Furthermore, regarding the preferred numerical range (e.g., the range of content, etc.), the lower and upper limits recorded in stages can be combined independently. For example, based on the description "preferably 10 to 90, more preferably 30 to 60", the "preferable lower limit (10)" and the "more preferably upper limit (60)" can be combined to obtain "10 to 60". Similarly, for example, based on the description "preferably 10 or more, more preferably 30 or more, and preferably 90 or less, more preferably 60 or less", "10 or more and 60 or less" can be selected as the preferred range, or only the range "60 or less" can be selected.

[0063] [Remove detection label]

[0064] The peel detection label of the present invention is a laminate formed by sequentially stacking a support, a pattern layer and an adhesive laminate, and satisfying the following requirement (1): the pattern layer is formed on a portion of the surface of the support, and the adhesive laminate has at least an adhesive layer (X) and a substrate layer (Y), wherein the elastic modulus of the substrate layer (Y) is 10 MPa or more and 800 MPa or less.

[0065] Requirement (1): When the peel detection label is pasted onto the adhered object and then peeled off from the adhered object, it is possible to visually detect whether the peel detection label has been peeled off from the adhered object based on the interface peeling that occurs between the support and the pattern layer.

[0066] This peel test label, by satisfying the above-described layer structure, becomes a peel test label that will not leave adhesive residue on the adhered object. Furthermore, by satisfying requirement (1), it becomes a material with excellent peel test performance.

[0067] The following, combined with Figure 1 and Figure 2 Preferred examples of peel detection tags according to embodiments of the present invention will be described, but the peel detection tags of the present invention are not limited to the following examples within the scope that can demonstrate the effects of the present invention.

[0068] Figure 1 This is a cross-sectional schematic diagram of a peel detection tag 101, illustrating an example of the structure of the peel detection tag of the present invention.

[0069] For example, the peel detection label of the present invention can be listed as follows. Figure 1 The peel detection label 101 shown is a peel detection label formed by sequentially stacking a support 1, a pattern layer 2, and an adhesive laminate 11 having an adhesive layer (X) 3 and a substrate layer (Y). Furthermore, the peel detection label of the present invention is... Figure 1 In the case of the peel detection label 101 shown, the adhesive laminate 11 is a laminate having an adhesive layer (X) 3 on the surface 4a side of the substrate layer (Y) 4. It can be an embodiment where the substrate layer (Y) 4 is in contact with the surface 1a of the support 1 where the pattern layer 2 is formed, and the pattern layer 2; or it can be an embodiment where the substrate layer (Y) 4 is in contact with the surface 1a of the support 1 where the pattern layer 2 is formed, and the surface 2a of the pattern layer 2 opposite to the support 1 side; or it can be... Figure 1 In the embodiment shown as the peel detection label 101, where the substrate layer (Y) 4 is in contact with the surface 1a of the support 1 on the side where the pattern layer 2 is formed, and covers the surface of the pattern layer 2 other than the surface in contact with the surface 1a of the support 1, it is preferable that in the adhesive laminate 11, the adhesive layer (X) 3 and the substrate layer (Y) 4 are directly laminated together in sequence.

[0070] Figure 2 This is a cross-sectional schematic diagram of a peel detection tag 102, illustrating an example of the structure of the peel detection tag of the present invention.

[0071] As a more preferred embodiment of the peeling detection tag of the present invention, examples can be listed. Figure 2 The peel test label 102 shown is a peel test label formed by sequentially stacking a support 1, a pattern layer 2 and a laminate (P1) (hereinafter also referred to as "laminate (P1)") 12, wherein the laminate (P1) is an adhesive laminate formed by sequentially stacking a first adhesive layer (X1) (hereinafter also referred to as "adhesive layer (X1)") 31, a substrate layer (Y) 4 and a second adhesive layer (X2) (hereinafter also referred to as "adhesive layer (X2)") 32. Figure 2 The embodiment shown illustrates an embodiment in which the adhesive laminate has adhesive layers (X) on both sides of the substrate layer (Y) 4. Regarding the two adhesive layers (X), the adhesive layer (X) located on the pattern layer side is designated as the first adhesive layer (X1) 31, and the adhesive layer (X) located on the substrate layer (Y) 4 opposite to the adhesive layer (X1) 31 is designated as the second adhesive layer (X2) 32.

[0072] At once Figure 2 In the embodiment of the peel detection tag 102 shown, it can be an embodiment in which the adhesive layer (X1) 31 is in contact with the surface 1a of the support 1 on the side where the pattern layer 2 is formed and the pattern layer 2. A more preferred embodiment is an embodiment in which the adhesive layer (X1) 31 is in contact with the surface 1a of the support 1 on the side where the pattern layer 2 is formed and the surface 2a of the pattern layer 2 on the side opposite to the support 1. A more preferred embodiment is... Figure 2 In the embodiment shown as peel detection label 102, where the adhesive layer (X1) 31 is in contact with the surface 1a of the support 1 on the side where the patterned layer 2 is formed, and covers the surface of the patterned layer 2 other than the surface in contact with the surface 1a of the support 1, it is further preferred that in the laminate (P1) 12, the adhesive layer (X1) 31, the substrate layer (Y) 4 and the adhesive layer (X2) 32 are directly laminated together in sequence.

[0073] For the aforementioned "direct stacking", for example, in Figure 1 In the case of the peel detection label 101 shown, it refers to a configuration where there are no other layers between the adhesive layer (X) 3 and the substrate layer (Y) 4, and the two layers are in direct contact. Additionally, for example in... Figure 2In the case of the peel detection label 102 shown, it refers to a stacked state in which there are no other layers between the adhesive layer (X1) 31 and the substrate layer (Y) 4, and between the substrate layer (Y) 4 and the adhesive layer (X2) 32, but the three layers are in direct contact.

[0074] in addition, Figure 3 This is a cross-sectional schematic diagram, showing the... Figure 2 The peel detection label 102 shown is in the case where it is peeled off from the adhered object 40 after being pasted thereon, that is, the case where the peel detection label 102 is peeled off again.

[0075] The peel detection tag of the present invention is as follows: Figure 3 When the peel detection label 102 is peeled off from the adhered object 40 as shown, an interface peeling occurs between the support 1 and the pattern layer 2, creating a gap 50. This makes the pattern visible, allowing visual detection of whether the peel detection label 102 has been peeled off from the adhered object 40. That is, it is a peel detection label that satisfies requirement (1).

[0076] Alternatively, as another embodiment of the peel detection label, it may be configured such that a peeling material is further laminated on at least one of the surfaces of the support body selected from the side opposite to the adhesive laminate and the adhesive surface of the adhesive layer (X) (the surface opposite to the side in contact with the substrate layer (Y)) (not shown).

[0077] Alternatively, as another embodiment of the peel detection label described above, it may be configured as follows: an adhesive layer (Xn) formed of a composition of different forming materials is further laminated on the adhesive layer (X) (not shown), where n represents an integer of 3 or more.

[0078] Alternatively, as another embodiment of the peel detection label described above, it may be configured as follows: an intermediate layer (M) (e.g., a base layer, a metal vapor-deposited film, a coloring layer, etc.) formed by a composition of different forming materials is further laminated between the substrate layer (Y) and the adhesive layer (X) (not shown).

[0079] It should be noted that, as mentioned above, the peel detection label of the present invention is not limited to these embodiments within the scope of demonstrating the effects of the present invention.

[0080] The thickness of the peel detection label is preferably 5 to 150 μm, more preferably 10 to 100 μm, further preferably 20 to 80 μm, and even more preferably 30 to 70 μm. Here, in the embodiment where the peel detection label is further laminated with peeling material as described above, the thickness of the peel detection label refers to the total thickness of the peel detection label excluding the peeling material.

[0081] The thickness of the peel detection label can be determined using the method described in the examples.

[0082] The adhesive force of the peel detection label to the adhesive surface in contact with the adhered object is preferably 0.5 N / 25 mm or more, more preferably 1.0 N / 25 mm or more, further preferably 3.0 N / 25 mm or more, even more preferably 5.0 N / 25 mm or more, and even more preferably 8.0 N / 25 mm or more. In addition, it is preferably 40.0 N / 25 mm or less, more preferably 30.0 N / 25 mm or less, further preferably 25.0 N / 25 mm or less, even more preferably 20.0 N / 25 mm or less, and even more preferably 15.0 N / 25 mm or less.

[0083] The adhesive strength of the peel test label can be determined using the method described in the examples.

[0084] Furthermore, one preferred embodiment of the present invention provides a peel detection label that allows visual detection of the presence or absence of further peeling of the peel detection label upon re-peeling due to interfacial peeling between the support and the pattern layer. Therefore, a peel detection label with transparency sufficient to visually identify at least the change caused by the interfacial peeling from the support side of the peel detection label when it is adhered to the substrate is preferred; a peel detection label with transparency sufficient to visually identify information on the substrate is even more preferred. That is, more preferably, any object present on the other surface side of the peel detection label can be observed with the naked eye from the surface side of the support side of the peel detection label.

[0085] The following is a more detailed explanation of each component that constitutes the aforementioned peel detection label.

[0086] <Support>

[0087] As for the aforementioned support, there is no particular limitation as long as the support meets the above requirement (1) in the peel detection label. Preferably, the support has a surface that has been treated with a pear skin surface. Here, pear skin surface treatment refers to the treatment of processing the surface of the support to form a surface with fine irregularities. Pear skin surface generally refers to a surface that is rough like the surface of a pear skin. It should be noted that, in this specification, the fine irregularities of the "surface treated with a pear skin surface" can be irregular or regular in shape.

[0088] When the surface of the support on one side of the patterned layer is treated with a pear-skin surface, the interfacial adhesion between it and the substrate layer (Y) or adhesive layer (X1) described later is improved, and interfacial peeling can be more effectively prevented at their interface, which is therefore preferred. That is, it is preferred because it satisfies requirement (1).

[0089] Furthermore, for example, if one side of the aforementioned support has undergone a pear-skin surface treatment, and an interface peeling occurs between the support and the aforementioned pattern layer, creating a gap at the peeled portion, light is diffusely reflected onto the pear-skin surface exposed into the gap. This causes the peeled area to change from transparent to translucent or opaque, or to form a matte pattern, before and after peeling. Therefore, the visual recognizability of the peel detection label during re-peeling is improved, and this is preferred.

[0090] As described above, for the peel detection label, which is one of the preferred embodiments of the present invention, when the peel detection label is peeled off again, an interface peeling occurs between the support and the pattern layer, thereby allowing visual detection of whether the peel detection label has been peeled off again. Therefore, the support is preferably a support having transparency that, when the support is placed in the peel detection label, allows any object present on at least the other surface of the support to be observed with the naked eye from the surface side of the peel detection label on the support side.

[0091] Therefore, it is more preferable to have a support that has transparency that enables visual detection of the presence or absence of re-peeling of the peel detection label, and the surface on one side of the pattern layer formed thereon is a surface treated with a pear skin surface.

[0092] As the aforementioned support, a transparent plastic film is preferably used. Examples of materials for the plastic film include: acrylic resins such as poly(meth)acrylate; polyamides such as fully aromatic polyamides, nylon 6, nylon 66, and nylon copolymers; polyester resins such as polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, and polyarylates; polyurethane resins such as polyurethane acrylates; polyethylene resins; polypropylene resins; poly(4-methyl-1-pentene); polyvinyl chloride resins; polyvinylidene chloride resins; polyvinyl alcohol resins; ethylene-vinyl acetate copolymers; polystyrene resins; polycarbonate resins; norbornene resins; and cycloolefin resins. Among these materials, polyamides and polyester resins are preferred from the perspectives of transparency, cost, and versatility, and polyethylene terephthalate is more preferred.

[0093] In addition, examples of the aforementioned pear-skin surface treatments include: embossing using an embossing roller with a pear-skin surface, sandblasting (sand pad layer treatment), plasma treatment, chemical etching using solvents, kneading of transparent micro-resin particles, and micro-texturing treatment based on matte materials. From the viewpoints of cost and versatility, embossing using an embossing roller with a pear-skin surface or sandblasting is preferred, and sandblasting is more preferably preferred.

[0094] Therefore, as the support, it is more preferable to have a polyamide film or polyester resin as the material, on the side of the support forming the pattern layer, having a pear-skin surface treated. More preferably, it is a polyethylene terephthalate film on the side of the support forming the pattern layer, having a pear-skin surface treated.

[0095] The thickness of the aforementioned support is preferably 1–150 μm, more preferably 5–130 μm, even more preferably 10–80 μm, even more preferably 20–60 μm, and still even more preferably 30–50 μm.

[0096] The thickness of the support can be measured using the method described in the examples.

[0097] It should be noted that, within the scope where the effects of the present invention can be demonstrated—that is, within the scope where the transparency of the peel detection label is such that the degree of change caused by the aforementioned interface peeling can be visually identified—a printed receiving layer may be provided on the side of the support opposite to the adhesive laminate for design purposes and anti-counterfeiting purposes, thereby providing a printed layer. Furthermore, within the scope where the effects of the present invention can be demonstrated, a release agent layer may also be provided on the side of the support opposite to the adhesive laminate for the purpose of forming a winding tape.

[0098] <Pattern Layer>

[0099] The aforementioned pattern layer is necessary for visually detecting that the peeling detection label has been re-peeled when the peeling detection label is re-peeled. Furthermore, it is a layer formed in the peeling detection label from a material that satisfies the aforementioned requirement (1).

[0100] Furthermore, since it is preferable to latent the pattern layer before re-peeling the peel detection label, a transparent layer is preferred. By forming a transparent pattern layer, the changes before and after re-peeling the peel detection label become more obvious. Moreover, even when the peel detection label is affixed to the adhered object, information such as text or patterns on the surface of the adhered object can be identified by peeling the label, or the label itself becomes transparent and inconspicuous. From this point of view, it is preferred.

[0101] As for the patterned layer mentioned above, there is no particular limitation as long as the layer meets the above requirement (1) in the peel test label. Preferably, it is a layer formed by a composition of one or more selected from cellulose resins such as methylcellulose, carboxymethylcellulose, and hydroxyethylcellulose; acrylic resins such as poly(meth)acrylate and poly(methyl)acrylate; urethane resins; urethane acrylate resins; polyester resins such as polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, and polyarylate; and epoxy resins. More preferably, it is a layer formed by a composition of one or more selected from acrylic resins, urethane resins, urethane acrylate resins, and polyester resins. More preferably, it is a layer formed by a composition of one or more selected from acrylic resins and urethane acrylate resins. Even more preferably, it is a layer formed by a composition of acrylic resins.

[0102] The patterned layer is preferably a layer formed of a resin that forms an adhesive force lower than that of the adhesive layer (X), and more preferably a layer formed of a non-adhesive resin.

[0103] Therefore, the layer formed from the composition comprising an acrylic resin described above is preferably a layer formed from an acrylic resin that can form a layer with adhesive strength lower than that of the resin used in the adhesive layer (X), and more preferably a layer formed from a composition comprising an acrylic polymer whose main monomer is methyl methacrylate. Here, "main monomer" refers to the monomer component that has the highest content (amount used) among the monomer components forming the polymer.

[0104] Furthermore, from the viewpoint that it is easier for the interface peeling between the support and the pattern layer to occur when the peeling test label is peeled off again, and it is easier to meet the above requirement (1), it is preferable that the adhesive force between the pattern layer and the support is lower than the adhesive force between the adhesive laminate and the support. More preferably, the adhesive force between the pattern layer and the support is lower than the adhesive force between the adhesive laminate and the support, and also lower than the adhesive force between the pattern layer and the adhesive laminate.

[0105] From the same point of view, for example, when the pattern layer is covered by the substrate layer (Y), it is preferable that the adhesive force between the pattern layer and the support is lower than the adhesive force between the substrate layer (Y) and the support, and more preferably that the adhesive force between the pattern layer and the support is lower than the adhesive force between the substrate layer (Y) and the support, and also lower than the adhesive force between the pattern layer and the substrate layer (Y).

[0106] From the same point of view, when the adhesive laminate is a laminate (P1), it is preferable that the adhesive force between the pattern layer and the support is lower than the adhesive force between the adhesive layer (X1) and the support. More preferably, the adhesive force between the pattern layer and the support is lower than the adhesive force between the adhesive layer (X1) and the support, and also lower than the adhesive force between the pattern layer and the adhesive layer (X1).

[0107] Furthermore, this implementation method is preferred because it can more effectively prevent peeling at interfaces other than the interface between the support and the pattern layer. That is, it is preferred because requirement (1) is satisfied.

[0108] In the above-mentioned patterned layer, the total content of each of the above-mentioned resins is preferably 50% by mass or more, more preferably 70% by mass or more, further preferably 80% by mass or more, even more preferably 90% by mass or more, and preferably 100% by mass or less.

[0109] Furthermore, the pattern layer is formed on a portion of the surface of the support. If the pattern layer is formed on the entire surface of the support, peeling will occur across the entire interface between the support and the pattern layer, resulting in adhesive residue on the adhered object.

[0110] Here, the area of ​​the patterned layer formed on the surface of the support body is less than 100% of the area of ​​the surface on which the patterned layer is formed, whether in the actual state where the peel detection label is pasted or in the peel detection label after being punched to a given size for use. Preferably, it is 1 to 99%, more preferably 2 to 95%, further preferably 3 to 90%, even more preferably 5 to 80%, even more preferably 8 to 70%, even more preferably 10 to 60%, and even more preferably 12 to 45%.

[0111] The method for forming the pattern layer is not particularly limited as long as it is a method capable of forming a pattern layer on the support. For example, ink containing the resin and solvent described above can be used to form the pattern layer using conventional printing methods such as gravure printing, screen printing, offset printing, flexographic printing, etc.

[0112] Furthermore, there are no special restrictions on the shape of the resulting pattern, as long as the peeling of the detection label can be detected. It can be a geometric pattern or design, or it can be a text pattern.

[0113] It should be noted that the pattern is not necessarily limited to patterns based on a certain regular "configuration," but also includes irregular (random) shaped patterns. For example, it is not limited to printing specific regular shapes using the above printing methods. When only the pattern layer material is sprayed onto the support to obtain an irregular (random) shape, even if the label's hue and translucency change randomly in some areas and are visually identifiable, the areas formed by the pattern layer material on the support are also included in the pattern layer.

[0114] It should be noted that, from the perspectives of manufacturing and product quality, such as the need to more accurately and clearly detect the presence or absence of re-peeling of the peeling test label, and the need to form a pattern layer suitable for the size of the label when it is processed, it is preferable that the interface between the support and the pattern layer has a certain area or more. Therefore, it is preferable to form a given regular pattern.

[0115] Furthermore, as mentioned earlier, since the pattern layer itself can form a given pattern, when the pattern layer is a transparent layer, the pattern can be formed in the form of hidden patterns such as hidden text. Here, "hidden pattern" refers to a pattern that is hidden and cannot be visually detected before the detection label is peeled off again because the formed pattern is transparent, but becomes visible and can be visually detected after the detection label is peeled off again.

[0116] In addition, as mentioned above, the pattern layer used in this invention has the following advantages: since the pattern layer itself will peel off from the support at the interface, for example, as a pattern layer, there is no need to set up layers that separate their respective functions, such as release layers and printing layers.

[0117] Furthermore, by adopting the aforementioned structure of the peel detection label of the present invention, it is possible to achieve interface peeling between the support and the pattern layer, while effectively suppressing interface peeling in other parts. Therefore, even when the pattern layer itself forms a relatively complex pattern such as text, the degree to which the pattern can be visually detected can be achieved when the peel detection label is peeled off again.

[0118] The thickness of the pattern layer can be any thickness lower than that of the adhesive laminate described later. In the embodiment where the support is in contact with the substrate layer (Y) as described above, it is preferable to be thinner than the substrate layer (Y). Furthermore, in the embodiment where the adhesive laminate is a laminate (P1) described later, it is preferable to be thinner than the adhesive layer (X1). The thickness of the pattern layer is preferably 0.05 to 16 μm, more preferably 0.1 to 12 μm, and even more preferably 0.5 to 8 μm.

[0119] The thickness of the patterned layer can be measured using the method described in the examples.

[0120] <Adhesive Laminates>

[0121] The aforementioned adhesive laminate is a laminate having an adhesive layer (X) and a substrate layer (Y). As mentioned above, it is preferably a laminate having two or more adhesive layers (X), and more preferably an adhesive laminate formed by sequentially stacking a first adhesive layer (X1), a substrate layer (Y), and a second adhesive layer (X2), i.e., a laminate (P1).

[0122] <<Adhesive Layer (X)>>

[0123] The adhesive layer (X) is preferably a layer formed from a composition (x) containing an adhesive resin, and more preferably a layer formed by drying a coating film (x') formed from a composition (x) containing an adhesive resin.

[0124] Here, in this specification, "coating" refers to a film formed by a known coating method from a composition as a forming material, wherein the residual rate of volatile components such as solvents contained in the film is 10 to 100% by mass relative to the total amount of volatile components contained in the composition before coating.

[0125] That is, in this specification, the coating film contains a certain amount of volatile components such as solvents.

[0126] It should be noted that when the above-mentioned adhesive laminate has multiple adhesive layers (X), for example, when the above-mentioned adhesive laminate is a laminate (P1), in this specification, the compositions forming adhesive layers (X1) and adhesive layers (X2) in the compositions corresponding to the compositions (x) forming each adhesive layer (X) will be referred to as composition (x-1) and composition (x-2), respectively. In this case, similarly, the coatings corresponding to the coating film (x') will be referred to as coating film (x-1') and coating film (x-2'), respectively.

[0127] Furthermore, it is preferable that the pattern layer and the adhesive layer (X) contain resins of the same type. For example, if the pattern layer is formed of an acrylic resin, the adhesive layer (X) is also preferably an acrylic resin, as described later. By adopting such a solution, the interfacial adhesion between the adhesive layer (X) and the pattern layer is improved, making it easier to meet the above requirement (1), and therefore it is preferred.

[0128] For example, in the case where the adhesive laminate is a laminate (P1), for the same reason, it is preferable that the pattern layer and the adhesive layer (X1) contain resins of the same kind. For example, if the pattern layer is a layer formed of an acrylic resin, the adhesive layer (X1) is also preferably an acrylic resin as described later.

[0129] [Composition (x)]

[0130] The composition (x) that forms the adhesive layer (X) is a composition containing an adhesive resin.

[0131] It should be noted that, in one embodiment of the present invention, the components other than the adhesive resin contained in the composition (x) may be appropriately adjusted according to the intended use of the peel detection label according to the present invention.

[0132] For example, in one embodiment of the invention, from the viewpoint of adjusting the adhesive force to a desired range, the composition (x) may further contain one or more selected from tackifiers and crosslinking agents, and in addition to these, may contain one or more selected from diluents and adhesive additives used in conventional adhesives.

[0133] (Adhesive resin)

[0134] The weight-average molecular weight (Mw) of the aforementioned adhesive resin is preferably 10,000 to 2,000,000, more preferably 20,000 to 1,500,000, and even more preferably 30,000 to 1,000,000.

[0135] Examples of adhesive resins included in composition (x) include acrylic resins, urethane resins, polyisobutylene resins, olefin resins, urethane acrylate resins, and polyester resins, which satisfy the adhesive strength of the adhesive layer (X) described later. Among these adhesive resins, it is preferable to select one or more from acrylic resins, urethane resins, urethane acrylate resins, and polyester resins, and more preferably acrylic resins.

[0136] These adhesive resins can be used alone or in combination of two or more.

[0137] Furthermore, when these adhesive resins are copolymers having two or more structural units, there are no special limitations on the morphology of the copolymer; it can be any morphology among block copolymers, random copolymers, and graft copolymers.

[0138] Furthermore, from the viewpoint of further improving the interfacial adhesion between the adhesive layer (X) and the substrate layer (Y), these adhesive resins are preferably UV-non-curable adhesive resins that do not have polymerizable functional groups.

[0139] In the total amount (100% by mass) of the active ingredients in composition (x), the content of adhesive resin in composition (x) is preferably 30-99.99% by mass, more preferably 40-99.95% by mass, more preferably 50-99.90% by mass, further preferably 55-99.80% by mass, and even more preferably 60-99.50% by mass.

[0140] {Acrylic resins}

[0141] In one embodiment of the invention, from the viewpoint of further improving the interfacial adhesion with the substrate layer (Y), it is preferable that the adhesive resin contained in the composition (x) comprises an acrylic resin.

[0142] From the viewpoint of further improving interfacial adhesion, the proportion of acrylic resin contained in the adhesive resin is preferably 30 to 100% by mass, more preferably 50 to 100% by mass, further preferably 70 to 100% by mass, and even more preferably 85 to 100% by mass, in the total amount (100% by mass) of adhesive resin contained in the composition (x).

[0143] Examples of acrylic resins that can be used as adhesive resins include polymers containing structural units derived from alkyl (meth)acrylates having straight or branched alkyl groups, and polymers containing structural units derived from (meth)acrylates having cyclic structures.

[0144] The weight-average molecular weight (Mw) of the acrylic resin is preferably 100,000 to 1,500,000, more preferably 200,000 to 1,300,000, further preferably 350,000 to 1,200,000, and even more preferably 500,000 to 1,100,000.

[0145] As the aforementioned acrylic resin, an acrylic polymer (A0) having a structural unit (a1) derived from an alkyl methacrylate (a1') (hereinafter also referred to as "monomer (a1')") is preferred, and an acrylic copolymer (A1) having a structural unit (a1) and simultaneously having a structural unit (a2) derived from a functional group-containing monomer (a2') (hereinafter also referred to as "monomer (a2')") is more preferred.

[0146] From the viewpoint of improving adhesive properties, the number of carbon atoms of the alkyl group in the monomer (a1') is preferably 1 to 24, more preferably 1 to 12, further preferably 1 to 8, and even more preferably 4 to 6.

[0147] It should be noted that the alkyl group in the monomer (a1') can be either a straight-chain alkyl group or a branched-chain alkyl group.

[0148] Examples of monomers (a1') include: methyl methacrylate, ethyl methacrylate, propyl methacrylate, butyl methacrylate, 2-ethylhexyl methacrylate, lauryl methacrylate, tridecyl methacrylate, stearyl methacrylate, etc.

[0149] The monomer (a1') is preferably methyl methacrylate, butyl methacrylate, and 2-ethylhexyl methacrylate. Furthermore, when the adhesive laminate is a laminate (P1) and the adhesive layer (X) is an adhesive layer (X1), the monomer (a1') is more preferably methyl methacrylate and butyl methacrylate, and when the adhesive layer (X) is an adhesive layer (X2), the monomer (a1') is more preferably 2-ethylhexyl methacrylate and butyl methacrylate.

[0150] These monomers (a1') can be used alone or in combination of two or more.

[0151] Of all the structural units (100% by mass) of the acrylic polymer (A0) or acrylic copolymer (A1), the content of structural unit (a1) is preferably 50-100% by mass, more preferably 60-99.9% by mass, further preferably 70-99.5% by mass, and even more preferably 80-99.0% by mass.

[0152] The functional groups of the monomer (a2') refer to functional groups that can react with the crosslinking agent optionally contained in the composition (x) described below and become the starting point for crosslinking, or functional groups that have a crosslinking promoting effect, such as hydroxyl, carboxyl, amino, epoxy, etc.

[0153] That is, as monomers (a2'), examples include: hydroxyl-containing monomers, carboxyl-containing monomers, amino-containing monomers, epoxy-containing monomers, etc.

[0154] These monomers (a2') can be used alone or in combination of two or more.

[0155] As monomers (a2'), hydroxyl-containing monomers and carboxyl-containing monomers are preferred.

[0156] Examples of hydroxyl-containing monomers include: 2-hydroxyethyl methacrylate, 2-hydroxypropyl methacrylate, 3-hydroxypropyl methacrylate, 2-hydroxybutyl methacrylate, 3-hydroxybutyl methacrylate, 4-hydroxybutyl methacrylate, and other hydroxyalkyl methacrylates; unsaturated alcohols such as vinyl alcohol and allyl alcohol.

[0157] Examples of carboxyl-containing monomers include: (meth)acrylic acid, crotonic acid and other olefinic unsaturated monocarboxylic acids; fumaric acid, itaconic acid, maleic acid, citraconic acid and other olefinic unsaturated dicarboxylic acids and their anhydrides; 2-(acryloyloxy)ethyl succinate, 2-carboxyethyl meth)acrylic acid, etc.

[0158] As monomers (a2'), 2-hydroxyethyl (meth)acrylate and (meth)acrylic acid are preferred.

[0159] These monomers (a2') can be used alone or in combination of two or more.

[0160] Furthermore, when the adhesive laminate is a laminate (P1) and the adhesive layer (X) is an adhesive layer (X1), the monomer (a2') is more preferably 2-hydroxyethyl methacrylate, and when the adhesive layer (X) is an adhesive layer (X2), the monomer (a1') is more preferably containing both 2-hydroxyethyl methacrylate and (meth)acrylic acid.

[0161] Of all the structural units (100% by mass) of the above-mentioned acrylic copolymer (A1), the content of structural unit (a2) is preferably 0.1 to 40% by mass, more preferably 0.3 to 30% by mass, further preferably 0.5 to 20% by mass, and even more preferably 0.7 to 10% by mass.

[0162] The acrylic copolymer (A1) may further have structural units (a3) ​​derived from monomers (a3') other than monomers (a1') and (a2'). When the adhesive laminate is a laminate (P1) and the adhesive layer (X) is an adhesive layer (X1), it is preferable to have monomers (a3').

[0163] It should be noted that in the acrylic copolymer (A1), the content of structural units (a1) and (a2) in all structural units (100% by mass) of the acrylic copolymer (A1) is preferably 70-100% by mass, more preferably 80-100% by mass, further preferably 85-100% by mass, and even more preferably 90-100% by mass.

[0164] Examples of monomers (a3') include: olefins such as ethylene, propylene, and isobutylene; halogenated olefins such as vinyl chloride and vinylidene chloride; diene monomers such as butadiene, isoprene, and chloroprene; cyclic methacrylates such as cyclohexyl methacrylate, benzyl methacrylate, isobornyl methacrylate, dicyclopentyl methacrylate, dicyclopentenyl methacrylate, dicyclopentenoxyethyl methacrylate, and imide methacrylates; styrene, α-methylstyrene, vinyltoluene, vinyl formate, vinyl acetate, acrylonitrile, methacrylamide, methacrylonitrile, methacryloylmorpholine, and N-vinylpyrrolidone.

[0165] Vinyl acetate is preferred as the monomer (a3').

[0166] {Carbamate Resins}

[0167] As a urethane resin that can be used as an adhesive resin, there is no particular limitation as long as it is a polymer having one or more of urethane bonds and urea bonds in at least one of the main chain and side chain.

[0168] Specific examples of urethane resins include urethane prepolymers (UX) obtained by reacting polyols with polyisocyanate compounds.

[0169] It should be noted that urethane prepolymers (UX) can also be prepolymers obtained by further implementing a chain extension reaction using a chain extender.

[0170] The weight-average molecular weight (Mw) of the urethane resin is preferably 10,000 to 200,000, more preferably 12,000 to 150,000, even more preferably 15,000 to 100,000, and even more preferably 20,000 to 70,000.

[0171] Polyols that can be used as raw materials for urethane prepolymers (UX) include, for example, alkylene polyols, polyether polyols, polyester polyols, polyesteramide polyols, polyester / polyether polyols, polycarbonate polyols, etc. There are no special limitations as long as they are polyols, and they can also be difunctional diols or trifunctional triols.

[0172] These polyols can be used alone or in combination of two or more.

[0173] Among these polyols, diols are preferred from the viewpoints of ease of acquisition and reactivity, and alkylene diols are more preferred.

[0174] Examples of alkylene glycols include: alkane glycols such as 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, neopentanediol, and 1,6-hexanediol; alkylene glycols such as ethylene glycol, propylene glycol, diethylene glycol, and dipropylene glycol; polyalkylene glycols such as polyethylene glycol, polypropylene glycol, and polybutanediol; polyoxyalkylene glycols such as polytetramethylene glycol; and so on.

[0175] Among these alkylene glycols, from the viewpoint of suppressing gelation during the reaction with the chain extender, glycols with a weight-average molecular weight (Mw) of 1,000 to 3,000 are preferred.

[0176] Examples of polyisocyanate compounds that can serve as raw materials for urethane prepolymers (UX) include aromatic polyisocyanates, aliphatic polyisocyanates, and alicyclic polyisocyanates.

[0177] Examples of aromatic polyisocyanates include: 1,3-phenyl diisocyanate, 1,4-phenyl diisocyanate, 4,4'-diphenylmethane diisocyanate (MDI), 2,4-toluene diisocyanate (2,4-TDI), 2,6-toluene diisocyanate (2,6-TDI), 4,4'-toluidine diisocyanate, 2,4,6-triisocyanate toluene, 1,3,5-triisocyanate benzene, dimethoxyaniline diisocyanate, 4,4'-diphenyl ether diisocyanate, 4,4',4”-triphenylmethane triisocyanate, 1,4-tetramethylphenyldimethyl diisocyanate, 1,3-tetramethylphenyldimethyl diisocyanate, etc.

[0178] Examples of aliphatic polyisocyanates include: trimethylene diisocyanate, tetramethylene diisocyanate, hexamethylene diisocyanate (HMDI), pentamethylene diisocyanate, 1,2-propylidene diisocyanate, 2,3-butylidene diisocyanate, 1,3-butylidene diisocyanate, dodecamethylene diisocyanate, and 2,4,4-trimethylhexamethylene diisocyanate.

[0179] Examples of alicyclic polyisocyanates include: 3-isocyanate-methylene-3,5,5-trimethylcyclohexyl isocyanate (IPDI: isophorone diisocyanate), 1,3-cyclopentane diisocyanate, 1,3-cyclohexane diisocyanate, 1,4-cyclohexane diisocyanate, methyl-2,4-cyclohexane diisocyanate, methyl-2,6-cyclohexane diisocyanate, 4,4'-methylene bis(cyclohexyl isocyanate), 1,4-bis(isocyanate methyl)cyclohexane, etc.

[0180] It should be noted that these polyisocyanate compounds can also be trimethylolpropane adduct-type modifiers of the above-mentioned polyisocyanates, biuret-type modifiers obtained by reacting with water, or isocyanurate-type modifiers containing isocyanurate rings.

[0181] From the viewpoint of obtaining a urethane polymer with excellent adhesive properties, one or more of these polyisocyanate compounds are preferably selected from 4,4'-diphenylmethane diisocyanate (MDI), 2,4-toluene diisocyanate (2,4-TDI), 2,6-toluene diisocyanate (2,6-TDI), hexamethylene diisocyanate (HMDI), 3-isocyanatomethylene-3,5,5-trimethylcyclohexyl isocyanate (IPDI) and their modified forms. From the viewpoint of weather resistance, one or more of HMDI, IPDI and their modified forms are more preferably selected.

[0182] The isocyanate group content (NCO%) in the urethane prepolymer (UX), measured based on JIS K1603-1:2007, is preferably 0.5 to 12% by mass, more preferably 1 to 4% by mass.

[0183] As a chain extender, it is preferably a compound having at least two hydroxyl groups selected from at least one of amino groups, or a compound having three or more hydroxyl groups selected from at least one of amino groups.

[0184] As a compound having at least one of two hydroxyl and amino groups, it is preferably a compound selected from at least one of aliphatic diols, aliphatic diamines, alkanolamines, bisphenols, and aromatic diamines.

[0185] Examples of aliphatic diols include: alkane diols such as 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, neopentanediol, 1,6-hexanediol, and 1,7-heptanediol; alkylene diols such as ethylene glycol, propylene glycol, diethylene glycol, and dipropylene glycol; and so on.

[0186] Examples of aliphatic diamines include ethylenediamine, 1,3-propanediamine, 1,4-butanediamine, 1,5-pentanediamine, and 1,6-hexanediamine.

[0187] Examples of alkanolamines include monoethanolamine, monopropanolamine, and isopropanolamine.

[0188] Examples of bisphenols include bisphenol A.

[0189] Examples of aromatic diamines include diphenylmethane diamine, toluene diamine, and phenyl dimethyl diamine.

[0190] Examples of compounds having three or more hydroxyl and amino groups include: polyols such as trimethylolpropane, di(trimethylolpropane), pentaerythritol, and dipentaerythritol; amino alcohols such as 1-amino-2,3-propanediol, 1-methylamino-2,3-propanediol, and N-(2-hydroxypropylethanolamine); ethylene oxide or propylene oxide adducts of tetramethylphenyldimethylamine; and so on.

[0191] {Polyisobutylene resins}

[0192] Polyisobutylene resins (hereinafter also referred to as "PIB resins") that can be used as adhesive resins are not particularly limited as long as they have a polyisobutylene backbone in at least one of the main chain and side chain.

[0193] The weight-average molecular weight (Mw) of the PIB resin is preferably 20,000 or more, more preferably 30,000 to 1,000,000, further preferably 50,000 to 800,000, and even more preferably 70,000 to 600,000.

[0194] Examples of PIB-type resins include: isobutylene homopolymers, such as polyisobutylene, copolymers of isobutylene and isoprene, copolymers of isobutylene and n-butene, copolymers of isobutylene and butadiene, and halogenated butyl rubbers made by brominating or chlorinating these copolymers.

[0195] It should be noted that when the PIB resin is a copolymer, the structural unit formed by isobutylene has the highest content among all structural units.

[0196] Of all the structural units (100% by mass) of the PIB resin, the content of structural units formed by isobutylene is preferably 80-100% by mass, more preferably 90-100% by mass, and even more preferably 95-100% by mass.

[0197] These PIB resins can be used alone or in combination of two or more.

[0198] In addition, when using PIB resins, it is preferable to use a combination of PIB resins with high weight-average molecular weight (Mw) and PIB resins with low weight-average molecular weight (Mw).

[0199] More specifically, it is preferable to use a combination of PIB resin (pb1) with a weight-average molecular weight (Mw) of 270,000 to 600,000 (hereinafter also referred to as "PIB resin (pb1)") and PIB resin (pb2) with a weight-average molecular weight (Mw) of 50,000 to 250,000 (hereinafter also referred to as "PIB resin (pb2)").

[0200] By using PIB-type resins (pb1) with high weight-average molecular weight (Mw), the durability and weather resistance of the formed adhesive layer can be improved, while the adhesion strength can also be enhanced.

[0201] In addition, by using a PIB resin (pb2) with a low weight-average molecular weight (Mw), it can be well compatible with PIB resin (pb1) and appropriately plasticize PIB resin (pb1), thereby improving the wettability of the adhesive layer relative to the adhered object and improving the adhesive properties, flexibility, etc.

[0202] The weight-average molecular weight (Mw) of PIB-type resins (pb1) is preferably 270,000 to 600,000, more preferably 290,000 to 480,000, further preferably 310,000 to 450,000, and even more preferably 320,000 to 400,000.

[0203] The weight-average molecular weight (Mw) of PIB-type resins (pb2) is preferably 50,000 to 250,000, more preferably 80,000 to 230,000, further preferably 140,000 to 220,000, and even more preferably 180,000 to 210,000.

[0204] The preferred proportion of PIB resin (pb2) to 100 parts by weight of PIB resin (pb1) is 5 to 55 parts by weight, more preferably 6 to 40 parts by weight, further preferably 7 to 30 parts by weight, and even more preferably 8 to 20 parts by weight.

[0205] {Olefin resins}

[0206] There are no particular limitations on olefin resins that can be used as adhesive resins, as long as they are polymers with structural units derived from olefin compounds such as ethylene and propylene.

[0207] This olefin resin can be used alone or in combination of two or more.

[0208] Specific examples of olefin resins include: low-density polyethylene, medium-density polyethylene, high-density polyethylene, and linear low-density polyethylene, polypropylene, copolymers of ethylene and propylene, copolymers of ethylene and other α-olefins, copolymers of propylene and other α-olefins, copolymers of ethylene and propylene and other α-olefins, and copolymers of ethylene and other olefin unsaturated monomers (ethylene-vinyl acetate copolymer, ethylene-(meth)acrylate alkyl ester copolymer, etc.).

[0209] Examples of the aforementioned α-olefins include: 1-butene, 1-pentene, 1-hexene, 1-heptene, 1-octene, 4-methyl-1-pentene, 4-methyl-1-hexene, etc.

[0210] Examples of the aforementioned olefinic unsaturated monomers include vinyl acetate, alkyl (meth)acrylates, and vinyl alcohol.

[0211] {Acrylate carbamate resins}

[0212] As urethane acrylate resins that can be used as adhesive resins, those urethane acrylate resins described below that have been appropriately adjusted in terms of the type and amount of monomer components and crosslinking agents to give them adhesive properties can be listed. There are no particular limitations on urethane acrylate resins that have adhesive properties.

[0213] {Polyester Resins}

[0214] Polyester resins that can be used as adhesive resins are not particularly limited to any polyester resin that possesses adhesive properties. Examples of the main components of such polyester resins (the resin components with the highest content (usage amount) in the polyester resin) include, for example, aromatic acid components such as terephthalic acid, isophthalic acid, methyl terephthalic acid, and naphthalene dicarboxylic acid, and random copolymers with diol components such as ethylene glycol, diethylene glycol, butanediol, and neopentyl glycol. It should be noted that polyester adhesives using these polyester resins are composed of polyester, solvents, crosslinking agents, tackifiers, etc., and the crosslinking system utilizes hydroxymethyl condensation, ionic crosslinking, isocyanate crosslinking, epoxy crosslinking, etc.

[0215] (Thickening agent)

[0216] In one embodiment of the invention, when forming an adhesive layer (X) that further enhances the adhesive strength, the composition (x) preferably further contains a tackifier. Therefore, when the adhesive laminate is a laminate (P1), it is preferable that the adhesive strength of the adhesive layer (X1) is greater than that of the adhesive layer (X2), as described later. Thus, in this configuration, the composition (x-1) forming the adhesive layer (X1) preferably further contains a tackifier, more preferably the composition (x-1) forming the adhesive layer (X1) further contains a tackifier, and the composition (x-2) forming the adhesive layer (X2) does not contain a tackifier.

[0217] Here, "tackifier" refers to an oligomer with a weight-average molecular weight (Mw) of less than 10,000 that helps improve the adhesive strength of adhesive resins. It is a component that is different from the adhesive resins mentioned above.

[0218] The weight-average molecular weight (Mw) of the tackifier is preferably 400 to 10,000, more preferably 500 to 8,000, and even more preferably 800 to 5,000.

[0219] Examples of tackifiers include: rosin resins such as rosin resin, rosin ester resin, and rosin-modified phenolic resin; hydrogenated rosin resins obtained by hydrogenating these rosin resins; terpene resins such as terpene resin, aromatic modified terpene resin, and terpene phenol resin; hydrogenated terpene resins obtained by hydrogenating these terpene resins; styrene resins obtained by copolymerizing styrene monomers such as α-methylstyrene or β-methylstyrene with aliphatic monomers; hydrogenated styrene resins obtained by hydrogenating these styrene resins; C5 petroleum resins obtained by copolymerizing C5 fractions such as pentene, isoprene, piperine, and 1,3-pentadiene generated during the thermal decomposition of naphtha, and hydrogenated petroleum resins of these C5 petroleum resins; C9 petroleum resins obtained by copolymerizing C9 fractions such as indene and vinyltoluene generated during the thermal decomposition of naphtha, and hydrogenated petroleum resins of these C9 petroleum resins; and so on.

[0220] These tackifiers can be used alone or in combination of two or more with different softening points and structures.

[0221] The softening point of the tackifier is preferably 60–170°C, more preferably 65–160°C, and even more preferably 70–150°C.

[0222] It should be noted that in this specification, the “softening point” of the tackifier is a value measured based on JIS K2531.

[0223] Furthermore, when using two or more types of tackifiers, it is preferable that the weighted average of the softening points of these tackifiers falls within the aforementioned range.

[0224] When composition (x) contains a tackifier, the content of the tackifier in composition (x) is preferably 0.01 to 65% by mass, more preferably 0.05 to 55% by mass, further preferably 0.1 to 50% by mass, even more preferably 0.5 to 45% by mass, and even more preferably 1.0 to 40% by mass in the total amount (100% by mass) of the active ingredients in composition (x).

[0225] It should be noted that, in the total amount (100% by mass) of the effective components of the composition (x), the total content of the adhesive resin and the tackifier in the composition (x) is preferably 70% by mass or more, more preferably 80% by mass or more, further preferably 85% by mass or more, even more preferably 90% by mass or more, and even more preferably 95% by mass or more.

[0226] (Cross-linking agent)

[0227] In one embodiment of the present invention, the composition (x) preferably contains an adhesive resin having the aforementioned functional groups, such as an acrylic copolymer having structural units (a1) and (a2), and also contains a crosslinking agent.

[0228] The crosslinking agent reacts with the functional groups of the adhesive resin, causing the resins to crosslink with each other.

[0229] Examples of crosslinking agents include: toluene diisocyanate, phenyl diisocyanate, hexamethylene diisocyanate, and their adducts, etc., which are isocyanate crosslinking agents; ethylene glycol glycidyl ether and other epoxy crosslinking agents; hexa[1-(2-methyl)aziridinyl]triazine triphosphine and other aziridinium crosslinking agents; aluminum chelates and other chelate crosslinking agents; and so on.

[0230] These crosslinking agents can be used alone or in combination of two or more. Among these crosslinking agents, isocyanate crosslinking agents are preferred from the viewpoints of improving cohesion and thus adhesive strength, as well as ease of acquisition.

[0231] The content of the crosslinking agent can be appropriately adjusted according to the number of functional groups present in the adhesive resin. For example, relative to 100 parts by weight of the aforementioned adhesive resin with functional groups, such as the acrylic copolymer, it is preferably 0.01 to 10 parts by weight, more preferably 0.03 to 7 parts by weight, and even more preferably 0.05 to 4 parts by weight.

[0232] (Additives for adhesives)

[0233] In one embodiment of the present invention, the composition (x) may also contain adhesive additives for general adhesives, other than the aforementioned tackifiers and crosslinking agents, within a range that does not impair the effects of the present invention.

[0234] Examples of additives used in this adhesive include: antioxidants, plasticizers, rust inhibitors, retardants, catalysts, and ultraviolet absorbers.

[0235] It should be noted that these adhesive additives can be used individually or in combination of two or more.

[0236] When these adhesive additives are included, the content of each adhesive additive is preferably 0.0001 to 20 parts by weight, more preferably 0.001 to 10 parts by weight, relative to 100 parts by weight of the adhesive resin.

[0237] (Diluting the solvent)

[0238] In one embodiment of the present invention, the composition (x) may also contain water and organic solvent as diluents in addition to the aforementioned various active ingredients, and be prepared in the form of a solution.

[0239] Examples of organic solvents include: toluene, xylene, ethyl acetate, butyl acetate, methyl ethyl ketone, diethyl ketone, methyl isobutyl ketone, methanol, ethanol, isopropanol, tert-butanol, sec-butanol, acetylacetone, cyclohexanone, n-hexane, and cyclohexane.

[0240] It should be noted that these diluents can be used alone or in combination of two or more.

[0241] When the composition (x) is in the form of a solution containing a diluent, the concentration of the active ingredient in the composition (x) is preferably 1 to 65% by mass, more preferably 5 to 60% by mass, even more preferably 10 to 50% by mass, even more preferably 25 to 45% by mass, and even more preferably 30 to 45% by mass.

[0242] The adhesive strength of the adhesive layer (X) is preferably 1.0 N / 25 mm or more, more preferably 5.0 N / 25 mm or more, further preferably 10.0 N / 25 mm or more, and even more preferably 14.0 N / 25 mm or more. Furthermore, the upper limit of the adhesive strength of the adhesive layer (X) is not particularly limited, but is preferably 40.0 N / 25 mm or less, more preferably 35.0 N / 25 mm or less, even more preferably 30.0 N / 25 mm or less, and even more preferably 25.0 N / 25 mm or less.

[0243] When the peel test label is in the form of an adhesive layer (X1) and an adhesive layer (X2), the adhesive force of the adhesive layer (X1) is preferably 1.0 N / 25 mm or more, more preferably 5.0 N / 25 mm or more, even more preferably 10.0 N / 25 mm or more, even more preferably 14.0 N / 25 mm or more, and even more preferably 18.0 N / 25 mm or more.

[0244] When the adhesive force of the adhesive layer (X1) meets the specified range, it can be considered that when the above-mentioned peel detection label is peeled off again, the interface between the support and / or pattern layer and the adhesive layer (X1) is not easy to peel off, and the adhesive layer (X1) itself is not easy to break. This can more effectively prevent residual adhesive on the adhered object, so it is preferred.

[0245] In addition, there is no particular limitation on the upper limit of the adhesive force of the adhesive layer (X1), but it is preferably 40.0N / 25mm or less, more preferably 35.0N / 25mm or less, further preferably 30.0N / 25mm or less, and even more preferably 25.0N / 25mm or less.

[0246] When the peel detection label is in the form of an adhesive layer (X1) and an adhesive layer (X2), the adhesive force of the adhesive layer (X2) is preferably 1.0 N / 25 mm or more, more preferably 5.0 N / 25 mm or more, even more preferably 10.0 N / 25 mm or more, and even more preferably 14.0 N / 25 mm or more. In addition, it is preferably 40.0 N / 25 mm or less, more preferably 30.0 N / 25 mm or less, even more preferably 25.0 N / 25 mm or less, and even more preferably 18.0 N / 25 mm or less.

[0247] When the adhesive force of the adhesive layer (X2) meets this range, for example when the peel detection label has a peeling material, it is easier to exhibit the function of not revealing the pattern when the peel detection label is peeled off from the peeling material, but revealing the pattern when the peel detection label is peeled off again, so it is preferred.

[0248] Furthermore, when the peel detection label has an adhesive layer (X1) and an adhesive layer (X2), it is preferable that the adhesive force of the adhesive layer (X1) is greater than that of the adhesive layer (X2). By making the adhesive force of the adhesive layer (X1) greater than that of the adhesive layer (X2), during the re-peeling of the peel detection label, it is more effective to prevent peeling at the interface between the support and / or pattern layer and the adhesive layer (X1) before the adhesive layer (X2) is peeled off from the adhered object, thus preventing the adhesive laminate from remaining on the adhered object and causing adhesive residue. Therefore, this is preferable. In addition, by making the adhesive force of the adhesive layer (X1) greater than that of the adhesive layer (X2), even in scenarios different from the originally envisioned situation, such as during the die-cutting process of the peel detection label, during manufacturing when the peel detection label is rolled or unrolled in roll form, during storage, and when the peel detection label is peeled off from the peeling material just before use, it is more effective to prevent the above-mentioned interface peeling from occurring. Therefore, this is preferable.

[0249] Furthermore, from the viewpoint of obtaining superior pattern visibility, the elastic modulus of the adhesive layer (X) is preferably 0.05 MPa or more, more preferably 0.08 MPa or more, even more preferably 0.10 MPa or more, even more preferably 0.12 MPa or more, and even more preferably 0.15 MPa or more. It is also preferably 0.70 MPa or less, more preferably 0.50 MPa or less, even more preferably 0.40 MPa or less, even more preferably 0.30 MPa or less, and even more preferably 0.25 MPa or less.

[0250] When the peel detection label is in the form of an adhesive layer (X1) and an adhesive layer (X2), the elastic modulus of the adhesive layer (X1) is preferably 0.05 MPa or more, more preferably 0.08 MPa or more, even more preferably 0.10 MPa or more, even more preferably 0.12 MPa or more, and even more preferably 0.15 MPa or more. In addition, it is preferably 0.70 MPa or less, more preferably 0.50 MPa or less, even more preferably 0.40 MPa or less, even more preferably 0.30 MPa or less, and even more preferably 0.25 MPa or less.

[0251] When the elastic modulus of the adhesive layer (X1) meets the specified range, the adhesive layer (X1) will not break and can deform sufficiently during the re-peeling of the aforementioned peel detection label. Therefore, it can be assumed that the deformation of the adhesive layer (X1) will cause the pattern layer to be elongated, thereby facilitating interfacial peeling between the support and the pattern layer. As a result, superior pattern visibility can be obtained, which is therefore preferred.

[0252] When the peel detection label is in the form of an adhesive layer (X1) and an adhesive layer (X2), the elastic modulus of the adhesive layer (X2) is preferably 0.05 MPa or more, more preferably 0.08 MPa or more, even more preferably 0.10 MPa or more, even more preferably 0.12 MPa or more, and even more preferably 0.15 MPa or more. In addition, it is preferably 0.70 MPa or less, more preferably 0.50 MPa or less, even more preferably 0.40 MPa or less, even more preferably 0.30 MPa or less, even more preferably 0.25 MPa or less, and even more preferably 0.18 MPa or less.

[0253] When the elastic modulus of the adhesive layer (X2) meets the specified range, the adhesive layer (X2) will deform sufficiently without breaking when the peel detection label is peeled off again, which can more effectively prevent the occurrence of undesirable conditions such as residual adhesive, and is therefore preferred.

[0254] Specifically, the adhesive force and elastic modulus of the adhesive layer (X) (which also includes adhesive layer (X1) and adhesive layer (X2)) can be determined by the methods described in the examples.

[0255] In addition, the adhesive strength and elastic modulus of the adhesive layer (X) can also be adjusted by adjusting the selection of the types and contents of the various components, such as the adhesive resin, tackifier, crosslinking agent and adhesive additives that form the adhesive layer, as mentioned above.

[0256] <<Substrate Layer (Y)>>

[0257] The elastic modulus of the substrate layer (Y) used in the peel detection label of the present invention is 10 MPa or more and 800 MPa or less. By making the substrate layer (Y) meet the above requirements, a peel detection label that does not leave adhesive residue on the adhered object can be obtained.

[0258] Furthermore, from the viewpoint of balancing the prevention of adhesive residue on the adhered object and superior pattern visibility, the elastic modulus of the substrate layer (Y) is preferably 15 MPa or more, more preferably 18 MPa or more, further preferably 50 MPa or more, even more preferably 100 MPa or more, and even more preferably 200 MPa or more. In addition, it is preferably 700 MPa or less, more preferably 600 MPa or less, even more preferably 500 MPa or less, even more preferably 400 MPa or less, and even more preferably 300 MPa or less.

[0259] Furthermore, from the viewpoint of obtaining better pattern visibility, it is preferable that the elastic modulus of the substrate layer (Y) is lower than that of the support, and more preferably that the elastic modulus of the substrate layer is lower than that of the support and higher than that of the adhesive layer (X).

[0260] Regarding the elastic modulus of the substrate layer (Y), if the value is less than 100 MPa, it represents the storage modulus E' at 23°C as measured by the torsional shear method, while if the value exceeds 100 MPa, it represents the storage modulus E' at 23°C as measured by the tensile method. Specifically, the measurement can be performed using the method described in the examples.

[0261] As the substrate layer (Y), any layer that satisfies the aforementioned elastic modulus is acceptable. For example, a plastic film that satisfies the aforementioned elastic modulus, as described in the section on the support, can also be used as the substrate layer (Y). When using this plastic film, from the perspectives of transparency, cost, and versatility, a film formed from urethane acrylic resin, olefin resin, polyamide, or polyester resin is preferred. Alternatively, the substrate layer (Y) can also be a layer formed by drying a coating film containing a non-adhesive resin.

[0262] Furthermore, the preferred substrate layer (Y) is a layer formed from a composition (y) comprising one or more non-adhesive resins (y1) selected from urethane resins and olefin resins, and is even more preferably a layer formed by drying a coating film (y') formed from a composition (y) comprising one or more non-adhesive resins (y1) selected from urethane resins and olefin resins.

[0263] When the substrate layer (Y) is formed to dry the coating (y') formed by the composition (y), it becomes a non-stretched film or sheet, and therefore has particularly superior flexibility compared to a substrate layer (Y) made of a plastic film or sheet obtained by means such as melt extrusion molding.

[0264] Therefore, it can be considered that when the substrate layer (Y) is a layer formed by drying the coating (y') formed by the composition (y), when the above-mentioned peel test label is peeled off again, the substrate layer (Y) is more likely to undergo the deformation necessary for the pattern layer to be displayed, and it is not easy to break even when the tensile stress generated in the peel material test label is greater. Therefore, it is easy to achieve both better pattern display and residue prevention.

[0265] In this specification, the term "unstretched film or sheet" does not include films or sheets obtained by intentionally stretching them in a specific direction. An example excluded is the case where the rotational speed ratio between the rollers is intentionally adjusted for the purpose of applying stretch to the film or sheet, i.e., the case where a roll-to-roll manufacturing apparatus, which serves as a stretching machine, is used.

[0266] On the other hand, in a continuous manufacturing process, such as using a roll-to-roll manufacturing apparatus, if the material is stretched under stress applied in the direction of travel in an unavoidable manner, it can be regarded as an "unstretched film or sheet" without this limitation.

[0267] [Composition (y)]

[0268] The composition (y) used as the forming material of the substrate layer (Y) is preferably a composition comprising one or more non-adhesive resins (y1) selected from urethane resins and olefin resins.

[0269] It should be noted that, in one embodiment of the present invention, the components in the composition (y) other than the non-adhesive resin (y1) may be appropriately adjusted according to the intended use of the peel detection label according to the present invention.

[0270] For example, in one embodiment of the present invention, composition (y) may also contain resins other than urethane resins and olefin resins within a range that does not impair the effects of the present invention. In addition, it may contain one or more substrate additives selected from diluents and substrates contained in general adhesive sheets.

[0271] (Non-adhesive resin (y1))

[0272] The non-adhesive resin (y1) is preferably a resin belonging to the urethane acrylate resin or olefin resin.

[0273] When the non-adhesive resin (y1) is a copolymer having two or more structural units, the morphology of the copolymer is not particularly limited and can be any morphology among block copolymers, random copolymers and graft copolymers.

[0274] Furthermore, in one embodiment of the present invention, from the viewpoint of further improving the interfacial adhesion between the substrate layer (Y) and the adhesive layer (X), the non-adhesive resin (y1) included in the composition (y) is preferably an ultraviolet-free resin that does not have polymerizable functional groups.

[0275] In the total amount (100% by mass) of the active ingredients in the composition (y), the content of non-adhesive resin (y1) in the composition (y) is preferably 50-100% by mass, more preferably 65-100% by mass, further preferably 80-98% by mass, and even more preferably 90-96% by mass.

[0276] {Acrylate carbamate resins}

[0277] Examples of the aforementioned acrylate urethane resins include: reaction products of acrylic polyol compounds and isocyanate compounds, and copolymers formed by polymerizing linear urethane prepolymers (UY) with olefinically unsaturated groups at both ends and vinyl compounds (VY) containing (meth)acrylates.

[0278] Acrylic urethane resins (hereinafter also referred to as "acrylic urethane resins (I)"), which are reaction products of acrylic polyol compounds and isocyanate compounds, have a chemical structure in which the main chain of acrylic resin serves as the backbone and these molecules are cross-linked and cured by urethane bonds.

[0279] The acrylic resin, as the main chain, is rigid. Therefore, during the re-peeling of the testing label, the adhesive laminate is less prone to breakage compared to the tensile stress generated during the deformation process of the testing label. This is believed to help improve the effect of suppressing residual adhesive formation. Furthermore, since it also has excellent adhesion to the adhesive resin contained in the adhesive layer (X), it is believed to help improve the interfacial adhesion with the adhesive layer (X). Based on this effect, interfacial delamination between the adhesive layer (X) and the substrate layer (Y) can also be suppressed in the adhesive laminate, thus more effectively suppressing the formation of residual adhesive.

[0280] On the other hand, an acrylate resin (hereinafter also referred to as "acrylate resin (II)") is a copolymer formed by polymerizing a linear urethane prepolymer (UY) having olefin unsaturated groups at both ends and a vinyl compound (VY) containing (meth)acrylate. The linear urethane prepolymer (UY) has a backbone of the main chain as the backbone and has structural units derived from the vinyl compound (VY) containing (meth)acrylate at both ends of the linear urethane prepolymer (UY).

[0281] Because acrylic urethane resins (II) have sites derived from linear urethane prepolymers (UY) interposed between acrylic sites in the main chain backbone, the distance between crosslinking points is longer than that of acrylic urethane resins (I), and their molecular structure is more likely to form a two-dimensional structure (network structure).

[0282] Furthermore, since the main chain of the urethane prepolymer (UY) is linear, it exhibits high tensile strength when external force is applied. Therefore, it can be assumed that during the re-peeling of the detection label, the adhesive laminate easily deforms along with the label as it deforms, thus reducing the likelihood of breakage and helping to improve the effect of suppressing residual adhesive formation.

[0283] Furthermore, the side chains of the structural units derived from the vinyl compound (VY) containing (meth)acrylate have a structure that readily entangles with the adhesive resin in the adhesive layer (X).

[0284] Therefore, it can be concluded that using urethane acrylic resin (II) as the forming material of the substrate layer (Y) can help improve the interfacial adhesion with the adhesive layer (X). Based on this effect, it can also be concluded that interfacial delamination between the adhesive layer (X) and the substrate layer (Y) in the adhesive laminate can be suppressed, and the occurrence of residual adhesive can be more effectively suppressed.

[0285] The weight-average molecular weight (Mw) of the acrylate resin is preferably 20 million to 500,000, more preferably 40 million to 300,000, further preferably 50 million to 200,000, and even more preferably 10,000 to 150,000.

[0286] It should be noted that, in one embodiment of the present invention, the urethane acrylate resin included in the composition (y) as a non-adhesive resin (y1) is preferably an urethane acrylate resin (II).

[0287] The following describes urethane acrylate resins (I) and (II).

[0288] {{Acrylic carbamate resin (I)}}

[0289] The acrylic polyol compound used as a raw material for acrylate resin (I) is preferably an acrylic copolymer (B1) having a structural unit (b1) derived from alkyl methacrylate (b1') (hereinafter also referred to as "monomer (b1')") and a structural unit (b2) derived from hydroxyl-containing monomer (b2') (hereinafter also referred to as "monomer (b2')").

[0290] The number of carbon atoms in the alkyl group of the monomer (b1') is preferably 1 to 12, more preferably 4 to 8, and even more preferably 4 to 6.

[0291] It should be noted that the alkyl group in the monomer (b1') can be either a straight-chain alkyl group or a branched-chain alkyl group.

[0292] As a specific monomer (b1'), monomers that are the same as the aforementioned monomer (a1') can be listed.

[0293] It should be noted that the monomer (b1') can be used alone or in combination of two or more.

[0294] Among them, the monomer (b1') is preferably butyl (meth)acrylate and 2-ethylhexyl (meth)acrylate, more preferably butyl (meth)acrylate.

[0295] The content of structural unit (b1) is preferably 60-99.9% by mass, more preferably 70-99.7% by mass, and even more preferably 80-99.5% by mass, relative to all structural units (100% by mass) of the acrylic copolymer (B1).

[0296] In addition, as monomers (b2'), the same monomers as the hydroxyl-containing monomers that can be selected as the aforementioned monomers (a2') can be listed.

[0297] It should be noted that the monomer (b2') can be used alone or in combination of two or more.

[0298] Of all the structural units (100% by mass) of the acrylic copolymer (B1), the content of structural unit (b2) is preferably 0.1 to 40% by mass, more preferably 0.3 to 30% by mass, and even more preferably 0.5 to 20% by mass.

[0299] In addition, the acrylic copolymer (B1) may further have structural units (b3) derived from other monomers (b3') besides monomers (b1') and (b2').

[0300] As monomers (b3'), the same monomers as the functionalized monomers other than the hydroxyl-containing monomers that can be selected as the aforementioned monomers (a2') and the aforementioned monomers (a3') can be listed.

[0301] It should be noted that, in all structural units (100% by mass) of the acrylic copolymer (B1), the content of structural units (b1) and (b2) is preferably 70-100% by mass, more preferably 80-100% by mass, further preferably 90-100% by mass, and even more preferably 95-100% by mass.

[0302] On the other hand, the isocyanate compounds that serve as raw materials for urethane resins (I) can be the same as the polyisocyanate compounds that serve as raw materials for urethane prepolymers (UX) mentioned above.

[0303] Among these, from the viewpoint of tensile properties when an external force is applied, isocyanate compounds without aromatic rings are preferred as isocyanate compounds, and aliphatic polyisocyanates and alicyclic polyisocyanates are more preferred.

[0304] In the urethane acrylate resin (I), the ratio of structural units derived from acrylic polyol compounds to structural units derived from isocyanate compounds [acrylic polyol compound / isocyanate compound] by mass is preferably 10 / 90 to 90 / 10, more preferably 20 / 80 to 80 / 20, further preferably 30 / 70 to 70 / 30, and even more preferably 40 / 60 to 60 / 40.

[0305] {{Acrylic carbamate resin (II)}}

[0306] Linear urethane prepolymers (UY) that serve as raw materials for acrylic urethane resins (II) can be exemplified by the reaction products of diols and diisocyanate compounds.

[0307] The diol and diisocyanate compounds can be used alone or in combination of two or more.

[0308] The weight-average molecular weight (Mw) of the linear urethane prepolymer (UY) is preferably 10,000 to 300,000, more preferably 30,000 to 200,000, further preferably 50,000 to 100,000, even more preferably 10,000 to 80,000, and still more preferably 20,000 to 60,000.

[0309] Examples of diols constituting linear urethane prepolymers (UY) include: alkylene glycols, polyether glycols, polyester glycols, polyesteramide glycols, polyester-polyether glycols, and polycarbonate glycols.

[0310] Among these diols, polycarbonate-type diols are preferred.

[0311] Examples of diisocyanate compounds constituting linear urethane prepolymers (UY) include aromatic diisocyanates, aliphatic diisocyanates, and alicyclic diisocyanates. From the viewpoint of tensile properties when subjected to external force, alicyclic diisocyanates are preferred.

[0312] It should be noted that, as specific diisocyanate compounds, those compounds that are diisocyanate compounds can be listed among the aforementioned examples of polyisocyanates that serve as raw materials for urethane prepolymers (UX).

[0313] Alternatively, linear urethane prepolymers (UY) can also be prepolymers obtained by performing a chain extension reaction using diols and diisocyanate compounds, along with a chain extender.

[0314] As a chain extender, the same chain extenders exemplified above as those that can be used in the synthesis of urethane prepolymers (UX) can be listed.

[0315] In one embodiment of the present invention, the linear urethane prepolymer (UY) is a prepolymer having olefinic unsaturated groups at both ends.

[0316] As a method for introducing olefinic unsaturated groups to both ends of a linear urethane prepolymer (UY), one example is the reaction of the terminal NCO group of a urethane prepolymer obtained by reacting a diol and a diisocyanate compound with a hydroxyalkyl ester of (meth)acrylate.

[0317] Examples of hydroxyalkyl esters of (meth)acrylate include: 2-hydroxyethyl ester of (meth)acrylate, 2-hydroxypropyl ester of (meth)acrylate, 3-hydroxypropyl ester of (meth)acrylate, 2-hydroxybutyl ester of (meth)acrylate, 3-hydroxybutyl ester of (meth)acrylate, 4-hydroxybutyl ester of (meth)acrylate, etc.

[0318] The vinyl compound (VY) used as a raw material for acrylate resin (II) contains at least (meth)acrylate.

[0319] As (meth)acrylates, those compounds that are the same as those in the monomers (a1') to (a3') used as raw materials for acrylic copolymers (A1) mentioned above are (meth)acrylates.

[0320] The (meth)acrylate is preferably selected from one or more of alkyl (meth)acrylate and hydroxyalkyl (meth)acrylate, and more preferably a combination of alkyl (meth)acrylate and hydroxyalkyl (meth)acrylate.

[0321] When alkyl (meth)acrylate and hydroxyalkyl (meth)acrylate are used in combination, the proportion of hydroxyalkyl (meth)acrylate to 100 parts by weight of alkyl (meth)acrylate is preferably 0.1 to 100 parts by weight, more preferably 0.2 to 90 parts by weight, further preferably 0.5 to 30 parts by weight, even more preferably 1.0 to 20 parts by weight, and still more preferably 1.5 to 10 parts by weight.

[0322] The number of carbon atoms of the alkyl group in the (meth)acrylate is preferably 1 to 24, more preferably 1 to 12, further preferably 1 to 8, and even more preferably 1 to 3.

[0323] As for the alkyl methacrylate, the same ones as those exemplified above as monomers (a1') that are raw materials for acrylic copolymers (A1) can be listed.

[0324] In addition, as hydroxyalkyl methacrylates, the same types as those exemplified above as hydroxyalkyl methacrylates used to introduce olefinic unsaturated groups to both ends of a linear urethane prepolymer (UY) can be listed.

[0325] Examples of vinyl compounds other than (meth)acrylates include: aromatic hydrocarbon vinyl compounds such as styrene, α-methylstyrene, and vinyltoluene; vinyl ethers such as methyl vinyl ether and ethyl vinyl ether; monomers containing polar groups such as vinyl acetate, vinyl propionate, (meth)acrylonitrile, N-vinylpyrrolidone, (meth)acrylic acid, maleic acid, fumaric acid, itaconic acid, and (meth)acrylamide; and so on.

[0326] These compounds can be used alone or in combination of two or more.

[0327] In one embodiment of the present invention, the content of (meth)acrylate in the vinyl compound (VY) used as a raw material for urethane resin (II) is preferably 40 to 100% by mass, more preferably 65 to 100% by mass, further preferably 80 to 100% by mass, and even more preferably 90 to 100% by mass, in the total amount (100% by mass) of the vinyl compound (VY).

[0328] In one embodiment of the present invention, the total content of alkyl (meth)acrylate and hydroxyalkyl (meth)acrylate in the vinyl compound (VY) used as a raw material for urethane resin (II) is preferably 40 to 100% by mass, more preferably 65 to 100% by mass, further preferably 80 to 100% by mass, and even more preferably 90 to 100% by mass in the total amount (100% by mass) of the vinyl compound (VY).

[0329] Acrylic urethane resins (II) can be obtained by polymerizing linear urethane prepolymers (UY) as raw materials with vinyl compounds (VY).

[0330] As a specific polymerization method, the vinyl compound (VY) can be synthesized in an organic solvent along with a linear urethane prepolymer (UY) and a vinyl compound (VY) as raw materials, in conjunction with a free radical generator, through a free radical polymerization reaction of the vinyl compound (VY) starting from the olefinic unsaturated groups at both ends of the linear urethane prepolymer (UY).

[0331] Examples of free radical generators used include diazo compounds such as azobisisobutyronitrile (DISI), and benzoyl peroxide.

[0332] It should be noted that in this free radical polymerization reaction, chain transfer agents such as thiol-containing compounds can also be added to the solvent to adjust the degree of polymerization of acrylic acid.

[0333] In one embodiment of the present invention, the content ratio of structural units derived from linear urethane prepolymer (UY) to structural units derived from vinyl compound (VY) [(UY) / (VY)], by mass ratio, is preferably 10 / 90 to 80 / 20, more preferably 20 / 80 to 70 / 30, further preferably 30 / 70 to 60 / 40, and even more preferably 35 / 65 to 55 / 45.

[0334] {Olefin resins}

[0335] As an olefin resin included in the composition (y) as a non-adhesive resin (y1), it is a polymer having at least structural units derived from olefin monomers.

[0336] As the olefin monomers mentioned above, α-olefins with 2 to 8 carbon atoms are preferred, and specific examples include ethylene, propylene, butene, isobutene, 1-hexene, etc.

[0337] Among these monomers, ethylene and propylene are preferred.

[0338] Specific examples of olefin resins include: ultra-low density polyethylene (VLDPE, density: 880 kg / m³). 3 Above and below 910 kg / m 3 Low-density polyethylene (LDPE, density: 910 kg / m³) 3 Above and below 915 kg / m 3 Medium-density polyethylene (MDPE, density: 915 kg / m³) 3 Above and below 942 kg / m 3 High-density polyethylene (HDPE, density: 942 kg / m³) 3 The above), linear low-density polyethylene and other polyethylene resins; polypropylene resin (PP); polybutene resin (PB); ethylene-propylene copolymer; olefin elastomer (TPO); ethylene-vinyl acetate copolymer (EVA); ethylene-propylene-(5-ethylidene-2-norbornene) and other olefin terpolymers; etc.

[0339] In one embodiment of the present invention, the olefin resin may also be a modified olefin resin that has undergone one or more modifications selected from acid modification, hydroxyl modification and acrylic modification.

[0340] For example, as an acid-modified olefin resin obtained by acid modification of an olefin resin, a modified polymer obtained by grafting and polymerizing an unsaturated carboxylic acid or its anhydride onto the aforementioned unmodified olefin resin can be cited.

[0341] Examples of unsaturated carboxylic acids or their anhydrides mentioned above include: maleic acid, fumaric acid, itaconic acid, citraconic acid, pentenoic acid, tetrahydrophthalic acid, aconitic acid, (meth)acrylic acid, maleic anhydride, itaconic anhydride, pentenoic anhydride, citraconic anhydride, aconitic anhydride, norbornene dicarboxylic acid, tetrahydrophthalic anhydride, etc.

[0342] It should be noted that unsaturated carboxylic acids or their anhydrides can be used alone or in combination of two or more.

[0343] Acrylic-modified olefin resins, which are obtained by modifying olefin resins with acrylic acid, can be exemplified by modified polymers obtained by grafting and polymerizing alkyl (meth)acrylates as side chains onto the aforementioned unmodified olefin resin as the main chain.

[0344] The number of carbon atoms in the alkyl group of the aforementioned (meth)acrylate is preferably 1 to 20, more preferably 1 to 16, and even more preferably 1 to 12.

[0345] Examples of the aforementioned alkyl (meth)acrylates include, for example, those compounds that are the same as those previously mentioned as being selectable as monomers (a1').

[0346] Hydroxyl-modified olefin resins, which are obtained by modifying olefin resins with hydroxyl groups, can be exemplified by modified polymers obtained by grafting hydroxyl-containing compounds onto the aforementioned unmodified olefin resin as the main chain.

[0347] As for the hydroxyl-containing compounds mentioned above, those that are the same as the aforementioned hydroxyl-containing monomers that can be selected as monomers (a2') can be listed.

[0348] The weight-average molecular weight (Mw) of the olefin resin is preferably 20 million to 1 million, more preferably 10,000 to 500,000, further preferably 20,000 to 400,000, and even more preferably 50,000 to 300,000.

[0349] (Resins other than acrylate resins and olefin resins)

[0350] In one embodiment of the present invention, the composition (y) may also contain resins other than urethane resins and olefin resins, within a range that does not impair the effects of the present invention.

[0351] Examples of such resins include: vinyl resins such as polyvinyl chloride, polyvinylidene chloride, polyvinyl alcohol, ethylene-vinyl acetate copolymer, and ethylene-vinyl alcohol copolymer; polyester resins such as polyethylene terephthalate, polybutylene terephthalate, and polyethylene naphthalate; polystyrene; acrylonitrile-butadiene-styrene copolymer; cellulose triacetate; polycarbonate; polyurethanes that are not acrylate resins; polymethylpentene; polysulfone; polyetheretherketone; polyethersulfone; polyphenylene sulfide; polyetherimide, polyimide, and other polyimide resins; polyamide resins; acrylic resins; and fluorinated resins.

[0352] From the viewpoint of further improving the interfacial adhesion between the substrate layer (Y) and the adhesive layer (X), it is preferable that the composition (y) contains a low proportion of resins other than urethane resins and olefin resins.

[0353] As for the specific proportion of resins other than acrylate resins and olefin resins, it is preferably less than 30 parts by mass, more preferably less than 20 parts by mass, even more preferably less than 10 parts by mass, further preferably less than 5 parts by mass, and even more preferably less than 1 part by mass, relative to 100 parts by mass of the total amount of non-adhesive resin (y1) selected from acrylate resins and olefin resins contained in the composition (y).

[0354] (Cross-linking agent)

[0355] In one embodiment of the invention, when the composition (y) contains an acrylate resin, it is more preferable to further contain a crosslinking agent in order to crosslink the acrylate resin.

[0356] As the crosslinking agent, isocyanate compounds are preferred, for example.

[0357] The isocyanate compound used as a crosslinking agent can be any compound that reacts with the functional groups of the above-mentioned acrylate resin to form a crosslinked structure; various isocyanate compounds can be used.

[0358] The preferred isocyanate compound is a polyisocyanate compound having two or more isocyanate groups per molecule.

[0359] Examples of polyisocyanate compounds include, for example, diisocyanates, triisocyanates, tetraisocyanates, pentaisocyanates, and hexaisocyanates. More specifically, examples include: aromatic polyisocyanates such as toluene diisocyanate, diphenylmethane diisocyanate, and phenylenediamine diisocyanate; alicyclic isocyanates such as dicyclohexylmethane-4,4-diisocyanate, bicycloheptane triisocyanate, cyclopentylene diisocyanate, cyclohexylene diisocyanate, methylcyclohexylene diisocyanate, and hydrogenated phenylenediamine diisocyanate; and aliphatic isocyanates such as pentamethyl diisocyanate, hexamethylene diisocyanate, heptamethyl diisocyanate, trimethylhexamethylene diisocyanate, and lysine diisocyanate.

[0360] Alternatively, these isocyanate compounds can be used as biuret bodies, isocyanurate bodies, or as adducts of the reaction products of these isocyanate compounds with non-aromatic low-molecular-weight compounds containing active hydrogen, such as ethylene glycol, trimethylolpropane, and castor oil.

[0361] Among these isocyanate compounds, aliphatic isocyanate compounds are preferred, aliphatic diisocyanate compounds are more preferred, and pentamethylene diisocyanate, hexamethylene diisocyanate, and heptamethylene diisocyanate are even more preferred.

[0362] In composition (y), the isocyanate compound can be used alone or in combination of two or more.

[0363] In the composition (y), the ratio of the above-mentioned acrylate resin to the isocyanate compound as a crosslinking agent, converted by solid components, is preferably 1 to 30 parts by mass, more preferably 2 to 20 parts by mass, and even more preferably 3 to 15 parts by mass, relative to 100 parts by mass of the total amount of the above-mentioned acrylate resin.

[0364] (catalyst)

[0365] In one embodiment of the present invention, when the composition (y) comprises an acrylate resin and the crosslinking agent described above, it is more preferable that the composition (y) further comprises a catalyst while containing the crosslinking agent described above.

[0366] The catalyst is preferably a metal catalyst, and more preferably a metal catalyst other than a tin compound having a butyl group.

[0367] Examples of metal-based catalysts include tin-based catalysts, bismuth-based catalysts, titanium-based catalysts, vanadium-based catalysts, zirconium-based catalysts, aluminum-based catalysts, and nickel-based catalysts. Among these, tin-based catalysts or bismuth-based catalysts are preferred, and tin-based catalysts or bismuth-based catalysts other than tin compounds containing a butyl group are more preferred.

[0368] As tin-based catalysts, examples of tin organometallic compounds include those with structures such as alkoxides, carboxylates, and chelates. Preferred examples include acetylacetone complexes, acetylacetone compounds, octanoic acid compounds, or cycloalkanoic acid compounds of these metals.

[0369] Similarly, bismuth-based catalysts, titanium-based catalysts, vanadium-based catalysts, zirconium-based catalysts, aluminum-based catalysts, or nickel-based catalysts can be exemplified by compounds of organometallic compounds of bismuth, titanium, vanadium, zirconium, aluminum, or nickel that have structures such as alkoxides, carboxylates, or chelates. Preferably, these metals can be exemplified by acetylacetone complexes, acetylacetone compounds, octanoic acid compounds, or naphthenic acid compounds.

[0370] Specific examples of acetylacetone complexes of metals include: tin acetylacetone, titanium acetylacetone, vanadium acetylacetone, zirconium acetylacetone, aluminum acetylacetone, nickel acetylacetone, etc.

[0371] Specific examples of acetylacetone compounds include: tin acetylacetone, bismuth acetylacetone, titanium acetylacetone, vanadium acetylacetone, zirconium acetylacetone, aluminum acetylacetone, nickel acetylacetone, etc.

[0372] Specific examples of octanoic acid compounds include: bismuth 2-ethylhexanoate, nickel 2-ethylhexanoate, zirconium 2-ethylhexanoate, tin 2-ethylhexanoate, etc.

[0373] Specific examples of cycloalkanoic acid compounds include: bismuth naphthenate, nickel naphthenate, zirconium naphthenate, tin naphthenate, etc.

[0374] As a tin-based catalyst, the general formula RzSn(L) is preferred. (4-z)(In this general formula, R is an alkyl group with 1 to 25 carbon atoms, preferably an alkyl group with 1 to 3 or 5 to 25 carbon atoms, or an aryl group, L is an organic group other than alkyl and aryl, or an inorganic group, and z is 1, 2 or 4) tin compound.

[0375] The above general formula RzSn(L) (4-z) In this molecule, the alkyl group of R is more preferably an alkyl group with 5 to 25 carbon atoms, and even more preferably an alkyl group with 5 to 20 carbon atoms. The number of carbon atoms of the aryl group of R is not particularly limited, but is preferably an aryl group with 6 to 20 carbon atoms. When there are two or more R groups in one molecule, each R group may be the same or different.

[0376] Furthermore, L is preferably an aliphatic carboxylic acid, aromatic carboxylic acid, or aromatic sulfonic acid with 2 to 20 carbon atoms, and more preferably an aliphatic carboxylic acid with 2 to 20 carbon atoms. Examples of aliphatic carboxylic acids with 2 to 20 carbon atoms include aliphatic monocarboxylic acids and aliphatic dicarboxylic acids with 2 to 20 carbon atoms. When there are two or more L atoms in one molecule, each L may be the same or different.

[0377] In the composition (y1), the catalyst can be used alone or in combination of two or more.

[0378] In the composition (y1), the ratio of the above-mentioned acrylate resin to the catalyst is as follows: relative to 100 parts by mass of the total amount of the above-mentioned acrylate resin, the catalyst, converted in solid form, is preferably 0.001 to 5 parts by mass, more preferably 0.01 to 3 parts by mass, and even more preferably 0.1 to 2 parts by mass.

[0379] (Additives for substrates)

[0380] In one embodiment of the invention, composition (y) may also contain substrate additives included in the substrate of a typical adhesive sheet, without compromising the effects of the invention.

[0381] Examples of additives used in such substrates include: ultraviolet absorbers, light stabilizers, antioxidants, antistatic agents, slip agents, and anti-blocking agents.

[0382] It should be noted that these additives for the substrate can be used individually or in combination.

[0383] When these substrate additives are included, the content of each substrate additive is preferably 0.0001 to 20 parts by mass, more preferably 0.001 to 10 parts by mass, relative to 100 parts by mass of the aforementioned non-adhesive resin.

[0384] (Diluting the solvent)

[0385] In one embodiment of the present invention, the composition (y) may also contain water and organic solvent as diluents in addition to the aforementioned various active ingredients, and thus be prepared in the form of a solution.

[0386] As organic solvents, those that are the same as those used when preparing the aforementioned composition (x) into a solution can be listed.

[0387] It should be noted that the diluent contained in the composition (y) can be used alone or in combination of two or more.

[0388] When the composition (y) is in the form of a solution containing a diluent, the concentration of each active ingredient in the composition (y) is preferably 0.1 to 60% by mass, more preferably 0.5 to 50% by mass, and even more preferably 1.0 to 40% by mass.

[0389] (Coloring agent)

[0390] The peel detection label preferably further includes a colorant in at least one layer selected from the adhesive layer (X) and the substrate layer (Y), and preferably includes the colorant in the substrate layer (Y).

[0391] By including at least one of the adhesive layer (X) and the substrate layer (Y) in a colorant, the visual recognizability of the peel detection pattern is further improved, making it easier to detect the presence or absence of re-peeling of the peel detection label.

[0392] Furthermore, as mentioned above, to improve the visual recognizability of the pattern, a metal vapor-deposited film layer or other coloring layers may be provided between the substrate layer (Y) and the adhesive layer (X). However, if at least one of the adhesive layer (X) and the substrate layer (Y) contains a colorant, it is preferable from the viewpoint that the adhesion at the interface with these other layers does not need to be considered, and the number of manufacturing steps can also be reduced. Similarly, from the viewpoint of reducing the impact on the adhesive strength of the adhesive layer (X), it is also preferable that the substrate layer (Y) contains a colorant.

[0393] The aforementioned coloring agent can be any coloring agent among pigments and dyes, preferably pigments.

[0394] The pigment can be any pigment, either inorganic or organic, but organic pigments are preferred.

[0395] Examples of inorganic pigments include carbon black and metal oxides. Carbon black is preferred for black inks.

[0396] Examples of organic pigments include: azo pigments, diazo pigments, phthalocyanine pigments, quinacridone pigments, isoindolinone pigments, and diazonium pigments. Phosphine pigments, naphthalene-based pigments, pyrene pigments, thioindigo pigments, anthraquinone pigments, and quinoline pigments.

[0397] Examples of dyes include: acid dyes, reactive dyes, direct dyes, oil-soluble dyes, disperse dyes, and cationic dyes.

[0398] There are no special restrictions on hue; any pigment or dye of any color, such as yellow, magenta, cyan, blue, red, orange, or green, can be used.

[0399] The colorants mentioned above can be used alone or two or more can be mixed in any proportion.

[0400] When at least one of the adhesive layer (X) and the substrate layer (Y) contains these colorants, the content of the colorant, in terms of solid content, is preferably 0.1 to 40 parts by weight, more preferably 1.0 to 35 parts by weight, and even more preferably 5.0 to 30 parts by weight, relative to 100 parts by weight of resin contained in each layer.

[0401] More preferably, the adhesive laminate is formed by directly laminating the coating (x') and the coating (y') in sequence and then removing the volatile components by simultaneously drying the coating (x') and the coating (y'). Furthermore, it is even more preferably an adhesive laminate formed by simultaneously applying the composition (x) and the composition (y) and then directly laminating the coating (x') and the coating (y') in sequence and then removing the volatile components by simultaneously drying the coating (x') and the coating (y').

[0402] When an adhesive laminate is formed by sequentially and directly laminating coatings (x) and (y') and then simultaneously drying them, the interfacial adhesion between the adhesive layer (X) and the substrate layer (Y) is higher compared to the case where an adhesive layer (X) is subsequently formed on a pre-formed substrate layer (Y). Therefore, it is preferred from the viewpoint of more effectively eliminating the generation of adhesive residue. This can be attributed to the fact that during the simultaneous drying of the coating (x') formed by the composition (x) which serves as the forming material of the adhesive layer (X) and the coating (y') formed by the composition (y) which serves as the forming material of the substrate layer (Y), interlayering of the coatings occurs near the interface, and the molecular chains of the resins contained in the compositions become entangled, thereby improving the interfacial adhesion between the adhesive layer (X) and the substrate layer (Y).

[0403] Furthermore, in the case of an adhesive laminate formed by simultaneously coating composition (x) and composition (y), compared with the case formed by coating each composition step by step, it is less likely to form a dry film on the surface of each coating film, so the adhesion between each layer is excellent, and therefore it is further preferred from the viewpoint of more effectively eliminating the generation of residual adhesive.

[0404] Similarly, when the above-mentioned adhesive laminate is a laminate (P1), it is more preferable to form an adhesive laminate (P1) formed by directly laminating the coating (x-1'), coating (y') and coating (x-2') in sequence, and then removing the volatile components by simultaneously drying the coating (x-1'), coating (y') and coating (x-2'). Furthermore, it is even more preferable to form an adhesive laminate (P1) formed by simultaneously applying the composition (x-1), composition (y) and composition (x-2), then directly laminating the coating (x-1'), coating (y') and coating (x-2') in sequence, and then removing the volatile components by simultaneously drying the coating (x-1'), coating (y') and coating (x-2').

[0405] Compared to the case where each composition is applied stepwise by simultaneously applying composition (x-1), composition (y), and composition (x-2), a dry film is less likely to form on the surface of each coating. Therefore, the resulting interlayer adhesion is excellent, which is preferred from the viewpoint of more effectively eliminating the generation of residual adhesive.

[0406] For the same reasons mentioned above, when the laminate (P1) is formed by directly laminating coatings (x-1'), coatings (y'), and coatings (x-2') in sequence and then drying coatings (x-1'), coatings (y'), and coatings (x-2') simultaneously, not only is the interfacial adhesion between the adhesive layer (X1) and the substrate layer (Y) better, but the interfacial adhesion between the adhesive layer (X2) and the substrate layer (Y) is also better than when the adhesive layer (X1) and adhesive layer (X2) are subsequently formed on the pre-formed substrate layer (Y), or when any of the remaining adhesive layers (X1) or (X2) are formed on the exposed surface of the substrate layer (Y) after the laminate of adhesive layer (X1) or (X2) and substrate layer (Y) is pre-formed using the aforementioned method. Therefore, from the viewpoint of more effectively eliminating the generation of residual adhesive, it is preferred.

[0407] Furthermore, in the case of an adhesive laminate (P1) formed by simultaneously coating composition (x-1), composition (y), and composition (x-2), compared to the case formed by progressively coating each composition, it is less likely to form a dry film on the surface of each coating film, thus resulting in excellent adhesion between the layers. Therefore, from the viewpoint of more effectively eliminating the generation of residual adhesive, it is even more preferred.

[0408] It should be noted that, in this invention, the adhesive laminate of the peel detection label is limited to the case where each layer is a coating layer, using the manufacturing method described above. However, in this case, it is sometimes necessary to use such a manufacturing method to limit it.

[0409] In other words, a method for determining whether or not a layer has formed can be considered, for example, by observing the interface between the substrate layer (Y) and the adhesive layer (X) using an electron microscope or similar means, through a cross-section in the thickness direction obtained by cutting the surface of the substrate layer (Y) of the laminate in a perpendicular direction, and judging whether or not it has formed based on the method of the present invention, according to the accompanying subjective visual perspective. However, when coatings are dried simultaneously to form each layer, especially when each layer is applied and dried simultaneously, the roughness of the interface is so small that it cannot be accurately measured, and the degree of roughness varies greatly depending on the area observed. Therefore, it is extremely difficult to evaluate using specific physical properties such as surface roughness.

[0410] In view of this situation, in the present invention, it is sometimes necessary to use the manufacturing method described above to limit the adhesive laminate of the peel detection label.

[0411] Regarding the aforementioned adhesive laminate, which is, for example, a laminate (P1) formed by sequentially and directly laminating coatings (x-1'), coatings (y'), and coatings (x-2') and simultaneously drying coatings (x-1'), coatings (y'), and coatings (x-2'), the relationship between the substrate layer (Y) and the adhesive layer (X1), and the relationship between the substrate layer (Y) and the adhesive layer (X2) are also the same.

[0412] The thickness of the adhesive laminate (the total thickness of the adhesive laminate) is preferably 2 to 100 μm, more preferably 4 to 80 μm, even more preferably 5 to 50 μm, even more preferably 10 to 40 μm, even more preferably 15 to 35 μm, and even more preferably 15 to 30 μm.

[0413] The thickness (Xt) of the adhesive layer (X) is preferably 0.5 to 50.0 μm, more preferably 1.0 to 30.0 μm, even more preferably 2.0 to 20.0 μm, even more preferably 3.0 to 15.0 μm, and even more preferably 4.0 to 12.0 μm.

[0414] The thickness (Yt) of the substrate layer (Y) is preferably 0.5 to 50.0 μm, more preferably 1.0 to 30.0 μm, even more preferably 2.0 to 20.0 μm, even more preferably 2.5 to 15.0 μm, and even more preferably 3.0 to 12.0 μm.

[0415] In this specification, the total thickness (total thickness) of the adhesive laminate is a value measured using a constant pressure thickness gauge based on JIS K6783-1994, Z1702-1994, and Z1709-1995, and can be specifically measured based on the methods described in the examples.

[0416] In addition, the thickness of each layer constituting the adhesive laminate can be measured using the same method as the total thickness of the adhesive laminate described above. Alternatively, it can be measured using, for example, the method described in the embodiments. The cross-section obtained by cutting the adhesive laminate along the thickness direction can be observed using a scanning electron microscope, and the thickness ratio of each layer can be measured separately. The total thickness of the adhesive laminate measured using the aforementioned method can then be calculated.

[0417] In the above-mentioned peel detection label, the ratio of the thickness (Xt) of the adhesive layer (X) to the thickness (Yt) of the substrate layer (Y) [(Xt) / (Yt)] is preferably 1 / 3 to 3 / 1, more preferably 2 / 5 to 5 / 2, and even more preferably 1 / 2 to 2 / 1.

[0418] It should be noted that, regarding the aforementioned thickness (Xt) and thickness ratio [(Xt) / (Yt)], in the case of multiple adhesive layers (X) having adhesive layers (X1) and adhesive layers (X2) as in a laminate (P1), the thickness (Xt) of the adhesive layer (X) has the same meaning as the thickness (X1t) of adhesive layer (X1) and the thickness (X2t) of adhesive layer (X2). That is, the preferred ranges of thickness (X1t), thickness (X2t), thickness ratio [(X1t) / (Yt)], and thickness ratio [(X2t) / (Yt)] are the same as those of the aforementioned thickness (Xt) and thickness ratio [(Xt) / (Yt)].

[0419] Furthermore, in the case where the aforementioned peel detection label has the aforementioned adhesive layer (Xn) (n is an integer of 3 or more) and intermediate layer (M), the thickness of each of these layers is not particularly limited within the range that can demonstrate the effects of the present invention.

[0420] It should be noted that when the above-mentioned adhesive laminate is an adhesive laminate with an adhesive layer (X) and a substrate layer (Y) formed by simultaneously drying the coating (x') and the coating (y') during the formation of the above-mentioned adhesive laminate, as described above, sometimes interlayering occurs between the coating of the adhesive layer (X) and the coating of the substrate layer (Y) during the drying process of the coating, making the interface between the adhesive layer (X) and the substrate layer (Y) unclear or even disappearing.

[0421] In cases where interlayer mixing occurs between coatings and between formed layers, for example, as described above, when observing a cross-section obtained by cutting the adhesive laminate along its thickness direction using a scanning electron microscope and measuring the thickness ratio of each layer, if interlayer mixing occurs between the adhesive layer (X) and the substrate layer (Y), it can be assumed that an interface exists at the midpoint of the thickness direction of the mixed layer and on a surface parallel to the opposite side of the adhesive layer (X) and the substrate layer (Y), and the thickness ratio of each layer is measured accordingly. The same applies when the adhesive laminate described above is an adhesive laminate (P1).

[0422] <Removal Material>

[0423] As described above, the peel detection tag, as one embodiment of the present invention, is, from an operational point of view, for example... Figure 1 The embodiment shown may further include a release material on the adhesive surface 3a of the adhesive layer (X) 3. Additionally, if, for example... Figure 2 The embodiment shown may further include a release material on the adhesive surface 12a of the adhesive laminate (P1) 12. Additionally, in Figure 1 or Figure 2 In any embodiment, the support 1 may be further provided with a release material on the surface opposite to the adhesive layer (X), and may be formed by clamping two release materials together. When using two release materials, the release materials may be the same or different from each other.

[0424] As a release material, release sheets that have undergone two-sided release treatment or single-sided release treatment can be used, and materials made by coating a release agent onto a substrate for release materials can be listed.

[0425] Examples of substrates used as release materials include: high-grade paper, cellophane, kraft paper, and other paper types; plastic films such as polyester resin films (polyethylene terephthalate resin, polybutylene terephthalate resin, polyethylene naphthalate resin, etc.), olefin resin films (polypropylene resin, polyethylene resin, etc.); and so on.

[0426] Examples of release agents include: silicone resins, olefin resins, isoprene resins, butadiene resins and other rubber elastomers, long-chain alkyl resins, alkyd resins, fluorinated resins, etc.

[0427] It should be noted that on the aforementioned surface of the adhesive layer (X) (e.g., if it is) Figure 1 The form shown is on the adhesive surface 3a of the adhesive layer (X) 3, or, if it is Figure 2 When a peeling material is used on the adhesive surface 12a of the adhesive laminate (P1) 12, it is preferable to use a peeling material that does not exhibit peeling force of the pattern layer when the peeling material is peeled off from the peel detection label, such as a material whose peeling force is adjusted so that no interfacial peeling occurs between the support and the pattern layer.

[0428] It should be noted that, as a method to effectively prevent the aforementioned interface peeling during the peeling of the release material, the method of treating the support surface with a pear-skin surface, as described above, can also be cited. The means of adjusting the peeling force of the release material and the aforementioned pear-skin surface treatment method can be used separately or in combination, but a combination is more preferred.

[0429] The thickness of the release material is not particularly limited, but is preferably 10-200 μm, more preferably 25-170 μm, even more preferably 30-125 μm, and even more preferably 50-100 μm.

[0430] [Manufacturing method for peeling off detection tags]

[0431] As a method for manufacturing the aforementioned peel detection label, it can be manufactured by, for example, obtaining a support with a patterned layer on one side of the support using the aforementioned method, and then further forming the aforementioned adhesive laminate on the support on the side with the patterned layer.

[0432] As methods for forming the aforementioned adhesive laminate, the following methods can be listed. It should be noted that in the following description, the manufacturing process is described as... Figure 1 and Figure 2 The following is an example of the structure of the peel-off detection label described above.

[0433] In manufacturing Figure 1 In the case of the peel detection label 101 shown, as previously described, a support 1 with a patterned layer 2 pre-formed on it is prepared (hereinafter also referred to as "support with patterned layer").

[0434] Next, a substrate layer (Y) 4 is formed on the side of the patterned support where the patterned layer 2 is formed, in a manner that covers the patterned layer 2. For example, the raw material for forming the substrate layer (Y) 4 can be heated and melted, then extruded and laminated onto the side of the patterned support where the patterned layer 2 is formed, or it can be subsequently coated onto the side of the patterned support where the patterned layer 2 is formed and dried to form a coating film made of a composition containing a non-adhesive resin that forms the substrate layer (Y) 4.

[0435] Next, an adhesive layer (X) 3 is formed on the side of the substrate layer (Y) 4 opposite to the support of the patterned layer. It should be noted that, when forming the adhesive layer (X) 3, for example, the raw material for forming the adhesive layer (X) 3 can be heated and melted, then extruded and laminated onto the substrate layer (Y) 4, or it can be subsequently coated onto the substrate layer (Y) 4 and dried to form a coating film (x') composed of an adhesive resin. Alternatively, for example, as the adhesive layer (X) 3, a material pre-extruded or dried from a coating film (x') can be directly adhered to the substrate layer (Y) 4.

[0436] As described above, when forming a laminate of adhesive layer (X) 3 and substrate layer (Y) 4, it is preferable to form an adhesive laminate by sequentially and directly laminating coating film (y') and coating film (x') on the surface of the support with patterned layer 2, and then simultaneously drying coating film (y') and coating film (x') to remove volatile components. Furthermore, it is more preferable to simultaneously apply composition (y) and composition (x) on the surface of the support with patterned layer 2, sequentially and directly laminating coating film (y') and coating film (x'), and then simultaneously drying coating film (y') and coating film (x') to remove volatile components.

[0437] In addition, for Figure 2 In the case of the peel detection label 102 shown, a support 1 with a patterned layer 2 pre-formed is also prepared as described above.

[0438] Next, an adhesive layer (X1) 31 is formed on the surface of the support with the patterned layer 2, covering the patterned layer 2. It should be noted that the adhesive layer (X1) 31 is a layer formed from a composition (x1) containing an adhesive resin. For example, the composition can be heated, melted, and then extruded and laminated onto the surface of the support with the patterned layer 2, or it can be subsequently coated onto the surface of the support with the patterned layer 2 and dried to form a coating film (x1') containing the adhesive resin composition (x1).

[0439] Next, a substrate layer (Y) 4 is formed on the side of the adhesive layer (X1) 31 opposite to the support of the patterned layer. It should be noted that, in forming the substrate layer (Y) 4, for example, the raw material for forming the substrate layer (Y) 4 can be heated and melted, then extruded and laminated onto the adhesive layer (X1) 31, or it can be subsequently coated onto the adhesive layer (X1) 31 and dried to form a coating film (y') formed from the composition (y). Alternatively, for example, as the substrate layer (Y) 4, a material pre-extruded or dried from a coating film (y') can be directly adhered to the adhesive layer (X1) 31.

[0440] It should be noted that, as mentioned above, when forming a laminate of adhesive layer (X1) 31 and substrate layer (Y) 4, it is preferable to form the laminate by sequentially and directly laminating the coating film (x-1') and coating film (y') on the surface of the support with patterned layer 2, and then simultaneously drying the coating film (x-1') and coating film (y') to remove volatile components. Furthermore, it is more preferable to simultaneously apply composition (x-1) and composition (y) to the surface of the support with patterned layer 2, sequentially and directly laminating the coating film (x-1') and coating film (y'), and then simultaneously drying the coating film (x-1') and coating film (y') to remove volatile components to form the laminate.

[0441] Next, an adhesive layer (X2) 32 is formed on the side of the formed substrate layer (Y) 4 opposite to the adhesive layer (X1) 31. It should be noted that, when forming the adhesive layer (X2) 32, for example, the composition (x2) containing an adhesive resin can be heated and melted, then extruded and laminated onto the substrate layer (Y) 4, or it can be subsequently coated onto the substrate layer (Y) 4 and dried to form a coating film (x2') formed from the composition (x2). Alternatively, for example, as the adhesive layer (X2), a material pre-extruded or dried from a coating film (x2') can be directly adhered to the substrate layer (Y) 4.

[0442] Alternatively, as another method for forming a substrate layer (Y) 4 on the side opposite to the support of the patterned layer on the formed adhesive layer (X1) 31, a laminate in which an adhesive layer (X2) 32 is formed by the above method on either side of the substrate layer (Y) 4 which is pre-extruded or dried by coating (y'), can be prepared in advance, and the exposed surface of the substrate layer (Y) 4 of the laminate can be directly adhered to the adhesive layer (X1) 31.

[0443] Alternatively, as another method for forming a substrate layer (Y) 4 on the side of the adhesive layer (X1) 31 opposite to the support of the patterned layer, a laminate can be prepared in advance, in which an adhesive layer (X2) 32 is formed on another pre-prepared release material by the above method, and a substrate layer (Y) 4 is formed on the side of the adhesive layer (X2) 32 opposite to the release material by the same method as described above. The exposed surface of the substrate layer (Y) 4 of the laminate is then directly adhered to the exposed surface of the adhesive layer (X1) 31.

[0444] As described above, when forming a laminate of adhesive layer (X2) 32 and substrate layer (Y) 4, it is preferable to remove volatile components by sequentially directly laminating coating film (x-2') and coating film (y') and then simultaneously drying coating film (x-2') and coating film (y'). Furthermore, it is more preferable to form the laminate by simultaneously applying composition (x-2) and composition (y), sequentially directly laminating coating film (x-2') and coating film (y'), and then simultaneously drying coating film (x-2') and coating film (y') to remove volatile components.

[0445] It should be noted that, as mentioned above, when forming a laminate (P1) consisting of an adhesive layer (X1) 31, a substrate layer (Y) 4, and an adhesive layer (X2) 32, it is even more preferable to form the laminate by sequentially and directly laminating a coating (x-1'), a coating (y'), and a coating (x-2') on the surface of the support with the patterned layer 2, and then simultaneously drying the coatings (x-1'), the coatings (y'), and the coatings (x-2') to remove volatile components. Furthermore, it is even more preferable to simultaneously apply compositions (x-1), compositions (y), and compositions (x-2) to the surface of the support with the patterned layer 2, and then sequentially and directly laminating the coatings (x-1'), the coatings (y'), and the coatings (x-2'), and then simultaneously drying the coatings (x-1'), the coatings (y'), and the coatings (x-2') to remove volatile components, thereby forming the laminate (P1).

[0446] It should be noted that, preferably, when forming the above-mentioned adhesive laminate (P1), the adhesive layer (X1) is formed in a manner that covers the above-mentioned pattern layer.

[0447] When gradually forming the aforementioned coatings, the coating machines used for coating each composition can include, for example, spin coaters, spray coaters, bar coaters, doctor blade coaters, roller coaters, doctor blade roller coaters, doctor blade coaters, gravure coaters, curtain coaters, and die coaters.

[0448] Furthermore, as a coating machine used when simultaneously coating various compositions, multilayer coating machines can be listed, specifically multilayer curtain coating machines, multilayer die coaters, etc. Among these coating machines, multilayer die coaters are preferred from an operability point of view.

[0449] It should be noted that, from the viewpoint of facilitating the formation of each coating film and improving productivity, it is preferable that each composition independently further contains a diluent.

[0450] As a diluent, the aforementioned diluents described in the stripping test label section can be used.

[0451] In addition, the effective ingredient concentration of the solution obtained by adding diluting solvent to each composition is as described in the peel test label section.

[0452] It should be noted that in the aforementioned manufacturing process, when multiple layers of coating are applied and then dried simultaneously, a pre-drying process can be performed before the simultaneous drying process and after one or more layers of coating are formed, to a degree that prevents the curing reaction of the coating from taking place.

[0453] For example, pre-drying can be performed at each stage of forming each layer of coating film (x-1') and coating film (y'), or pre-drying can be performed simultaneously on both coating films (x-1') and coating film (y') after they have been formed. From the viewpoint of improving the interfacial adhesion between the adhesive layer (X1) and the substrate layer (Y), it is preferable to perform pre-drying simultaneously on both coating films (x-1') and coating film (y') after they have been formed.

[0454] The drying temperature for pre-drying is typically set within a temperature range that does not cause the formed coating to cure, and is preferably lower than the drying temperature for simultaneous drying. Specifically, a drying temperature of 10–45°C is preferred, more preferably 10–34°C, and even more preferably 15–30°C.

[0455] Furthermore, the drying temperature for simultaneously drying the above-mentioned multilayer coatings is preferably 60 to 150°C, more preferably 70 to 145°C, even more preferably 80 to 140°C, and even more preferably 90 to 135°C.

[0456] [Use of peel-off detection tags]

[0457] As mentioned above, no adhesive residue is generated on the adhered object when using the peel detection label. Therefore, it is suitable for applications where adhesive residue is not desired on the adhered object and peel detection is required when peeling is necessary.

[0458] The following applications are foreseeable: for example, tamper-proofing of displays on automotive parts, electrical / electronic components, precision mechanical parts, etc.; preventing improper packing or opening of goods during transport or packaging; sealing labels to ensure the originality of contents of medicines, cosmetics, food, etc.; preventing improper opening and closing of various openings and closing mechanisms on vehicles such as cars, airplanes, trams, and ships (e.g., preventing improper entry of foreign objects into transport entrances, fuel tanks, etc.); preventing the removal or alteration of labels used for identification or certification of various documents such as passports and product certificates; security measures to prevent improper intrusion into various vehicles such as cars, airplanes, trams, and ships, and to prevent improper intrusion into various buildings; etc.

[0459] For the objects (attached objects) used in these applications, the peel detection label can be affixed and used. When peeled off from the attached object, as mentioned above, it is possible to visually detect whether the peel detection label has been peeled off from the attached object based on the interface peeling that occurs between the support and the pattern layer.

[0460] Example

[0461] The present invention will be described in more detail in the following embodiments, but the present invention is not limited to the following embodiments. It should be noted that the physical property values ​​in the following manufacturing examples and embodiments are values ​​measured using the following methods.

[0462] <Weight-average molecular weight (Mw)>

[0463] The values ​​were determined using a gel permeation chromatography apparatus (manufactured by Tosoh Corporation, product name "HLC-8020") under the conditions described below, and converted to standard polystyrene.

[0464] (Measurement conditions)

[0465] • Chromatographic column: Composed of “TSK guard column HXL-L”, “TSK gel G2500HXL”, “TSK gel G2000HXL”, and “TSK gel G1000HXL” (all manufactured by Tosoh Corporation) connected in sequence.

[0466] Column temperature: 40℃

[0467] • Developing solvent: tetrahydrofuran

[0468] • Flow rate: 1.0 mL / min

[0469] <Determination of Glass Transition Temperature>

[0470] Based on JIS K 7121, the measurements were performed using a differential scanning calorimeter (manufactured by TA Instruments Japan Co., Ltd., product name "DSC Q2000") at a heating rate of 20°C / min.

[0471] <Thickness of the support layer, pattern layer, adhesive laminate, and peel test label>

[0472] The measurement was performed using a constant pressure thickness gauge manufactured by TECLOCK Co., Ltd. (model number: "PG-02J", standard specifications: based on JIS K6783-1994, Z1702-1994, Z1709-1995).

[0473] It should be noted that the thickness of the pattern layer is obtained as follows: During the process of making the peel detection label of the test object, the total thickness of the overlapping part of the support and the pattern layer is measured in the state of the support with the pattern layer formed on the support, and then the thickness of the support that was measured in advance is subtracted, and the difference obtained is taken as the "thickness of the pattern layer".

[0474] The thickness of the adhesive laminate is obtained as follows: after measuring the total thickness of the peel detection label of the test object, the thickness of the support (where is the part of the unlaminated pattern layer) is subtracted, and the difference is taken as the "thickness of the adhesive laminate".

[0475] The total thickness of the peel test label was measured after removing the peel material from the adhesive layer (X2).

[0476] <Thickness of each layer in an adhesive laminate>

[0477] In the examples and comparative examples, a polyethylene terephthalate (PET) film (manufactured by Mitsubishi Chemical Corporation, trade name "DIAFOIL (registered trademark) T-100", thickness 50 μm) was laminated onto the adhesive layer (X2) of the peel test label to obtain the test sample.

[0478] Using a scanning electron microscope (manufactured by Hitachi, Ltd., product name "S-4700"), a cross-section in the thickness direction cut perpendicular to the surface of the adhesive layer (X2) of the test sample was observed, and the ratio (thickness ratio) of the thickness of each of the adhesive layer (X1), substrate layer (Y) and adhesive layer (X2) to the sum of the thicknesses of the adhesive layer (X1), substrate layer (Y) and adhesive layer (X2) was measured.

[0479] Furthermore, based on the thickness ratio of each layer, the thickness of each layer was calculated from the measured value of the "thickness of the adhesive laminate" determined using the aforementioned method. Table 1 shows the thickness ratio of each layer.

[0480] <Elastic modulus of substrate layer (Y), adhesive layer (X1) and adhesive layer (X2)>

[0481] The elastic modulus of the substrate layer (Y), adhesive layer (X1), and adhesive layer (X2) was determined using the following method.

[0482] Test samples with a diameter of 8 mm and a thickness of 3 mm were prepared from the same composition as the composition forming the layer to be measured. The shear storage modulus G' of the test sample at 23 °C was determined by torsional shear method using a viscoelasticity measuring apparatus (Anton Paar, MCR300) under the following conditions: test start temperature: -20 °C, test end temperature: 150 °C, heating rate: 3 °C / min, frequency: 1 Hz.

[0483] It should be noted that the value of the storage modulus E' was calculated from the value of the shear storage modulus G' based on the approximate formula "E' = 3G'".

[0484] In addition, for test samples with values ​​exceeding 100 MPa that cannot be measured using the aforementioned viscoelasticity measuring device, a dynamic viscoelasticity automatic measuring instrument (manufactured by Orientec Co., Ltd., product name "RHEOVIBRON (registered trademark) DDV-01FD") was used to measure the storage modulus E' of the test sample at 23°C by tensile method under the following conditions: test start temperature: -50°C, test end temperature: 200°C, heating rate: 3°C / min, amplitude: 5μm, frequency: 1Hz.

[0485] It should be noted that in Example 6, the material obtained by cutting the substrate layer (described later) into a size of 30 mm in the MD direction and 5 mm in the TD direction from the film (1) was directly used as the test sample. Furthermore, in Comparative Example 1, the substrate layer (Y) was essentially absent. In Comparative Example 2, instead of the substrate layer (Y), the adhesive layer (X) was used as the intermediate layer of the adhesive laminate. Regarding Comparative Examples 1 and 2, the elastic modulus of a single layer of the adhesive layer (X) was measured instead of the substrate layer (Y).

[0486] Additionally, MD in MD direction stands for Machine Direction, which refers to the length direction during the peel-off forming of the detection label. Similarly, TD in TD direction stands for Transverse Direction, which refers to the width direction during the peel-off forming of the detection label. Here, the "MD direction" of the substrate layer (Y) used in Examples 1-5 refers to the direction in which the coating composition is applied during film formation.

[0487] <Adhesive strength of adhesive layers (X1) and (X2)>

[0488] The adhesive strength of adhesive layers (X1) and (X2) was measured using the following method.

[0489] • Step (1): A 25 μm thick adhesive layer, formed from the same composition as the adhesive layer that forms the test object, was placed on a 25 μm thick polyethylene terephthalate (PET) film, and a test piece was made cut to a size of 300 mm in length and 25 mm in width.

[0490] • Step (2): In an environment of 23°C and 50% RH (relative humidity), the surface of the test piece with the adhesive layer exposed was attached to a stainless steel plate (SUS304 360 grit) and left to stand for 24 hours in the same environment.

[0491] • Step (3): Following step (2), the adhesive strength of the adhesive layer was measured at a tensile speed (peel speed) of 300 mm / min using the 180° peel method in an environment of 23°C and 50% RH (relative humidity), based on JIS Z0237:2000. The measured results were taken as the adhesive strength of the adhesive layer to be used.

[0492] Manufacturing Example 1

[0493] (Preparation of composition (x-1))

[0494] In 100 parts by weight (solid content ratio) of an acrylic copolymer (1) (an acrylic copolymer having structural units derived from raw material monomers of n-butyl acrylate (BA) / methyl methacrylate (MMA) / vinyl acetate (VAc) / 2-hydroxyethyl acrylate (2HEA) = 80.0 / 10.0 / 9.0 / 1.0 (mass ratio), weight average molecular weight (Mw): 1 million, diluent: ethyl acetate, solid content concentration: 45% by weight) as a tackifier, 25 parts by weight (solid content ratio) of hydrogenated rosin resin (manufactured by Arakawa Chemical Industry Co., Ltd., product name "KE-359", softening point: 94~104℃) as a tackifier, and isocyanate crosslinking agent (manufactured by Mitsui Chemicals Co., Ltd., product name "Takenate") as a crosslinking agent, 25 parts by weight (solid content ratio) of hydrogenated rosin resin (manufactured by Arakawa Chemical Industry Co., Ltd., product name "Takenate") as a crosslinking agent. 1.62 parts by weight of D-110N” (solid component ratio) were mixed and then diluted with toluene and stirred until homogeneous to prepare a composition (x-1) with a solid component concentration (active component concentration) of 40% by weight.

[0495] Manufacturing Example 2

[0496] (Preparation of composition (x-2))

[0497] In a 100-part (solids ratio) acrylic copolymer (2) (an acrylic copolymer having structural units derived from raw material monomers of n-butyl acrylate (BA) / 2-ethylhexyl acrylate (2EHA) / acrylic acid (AAc) / 2-hydroxyethyl acrylate (2HEA) = 47.0 / 47.0 / 5.5 / 0.5 (mass ratio), weight average molecular weight (Mw): 550,000, diluent: ethyl acetate, solids concentration: 40% by mass), 2 parts (solids ratio) of isocyanate crosslinking agent (manufactured by Tosoh Corporation, product name "Coronate L") as a crosslinking agent were mixed and then diluted with toluene and stirred until homogeneous to prepare a composition (x-2) with a solids concentration (active ingredient concentration) of 30% by mass.

[0498] Manufacturing Example 3

[0499] (Preparation of composition (ya))

[0500] (1) Synthesis of linear carbamate prepolymer (UY)

[0501] In a reaction vessel under a nitrogen atmosphere, 100 parts by weight (solids ratio) of polycarbonate diol with a weight average molecular weight (Mw) of 1,000 are mixed with isophorone diisocyanate, and the equivalent ratio of the hydroxyl groups of polycarbonate diol to the isocyanate groups of isophorone diisocyanate is 1 / 1. Then, 160 parts by weight of toluene are added, and the mixture is stirred under a nitrogen atmosphere and reacted at 80°C for more than 6 hours until the isocyanate group concentration reaches the theoretical amount.

[0502] Next, a solution prepared by diluting 1.44 parts by weight of 2-hydroxyethyl methacrylate (2-HEMA) in 30 parts by weight of toluene was added, and the reaction was further carried out at 80°C for 6 hours until the isocyanate groups at both ends disappeared, to obtain a linear urethane prepolymer (UY) with a weight average molecular weight (Mw) of 29,000.

[0503] (2) Synthesis of acrylate resin (II)

[0504] In a reaction vessel under a nitrogen atmosphere, add 100 parts by weight (solid content ratio) of the linear urethane prepolymer (UY) obtained in (1) above, 117 parts by weight (solid content ratio) of methyl methacrylate (MMA), 5.1 parts by weight (solid content ratio) of 2-hydroxyethyl methacrylate (2-HEMA), 1.1 parts by weight (solid content ratio) of 1-thioglycerol and 50 parts by weight of toluene, and heat to 105°C while stirring.

[0505] Then, over a further 4 hours, a solution prepared by diluting 2.2 parts by mass (solid component ratio) of free radical initiator (manufactured by Nippon Seika Co., Ltd., product name "ABN-E") with 210 parts by mass of toluene was added dropwise into the above reaction vessel while maintaining the temperature at 105°C.

[0506] After the above solution was added dropwise, the reaction was carried out at 105°C for 6 hours to obtain a solution of acrylate resin (II) with a weight-average molecular weight (Mw) of 105,000.

[0507] (3) Preparation of composition (ya)

[0508] In a solution of 100 parts by weight (solid content ratio) of the urethane acrylate resin (II) obtained in (2) above as a non-adhesive resin (y1), 6.3 parts by weight (solid content ratio) of hexamethylene diisocyanate crosslinking agent (manufactured by Tosoh Corporation, product name "Coronate HL") as a crosslinking agent and 1.4 parts by weight (solid content ratio) of dioctyltin bis(2-ethylhexanoate) as a catalyst were mixed. Then, the mixture was diluted with toluene and stirred until homogeneous to prepare a composition (ya) with a solid content concentration (active ingredient concentration) of 30% by weight.

[0509] Manufacturing Example 4

[0510] (Preparation of composition (yb))

[0511] A solution of an acid-modified olefin resin (manufactured by Mitsui Chemicals Co., Ltd., product name "UNISTOL H-200", weight average molecular weight (Mw): 145,000, glass transition temperature: -53°C, diluent: a mixture of methylcyclohexane and methyl ethyl ketone, solids concentration (active ingredient concentration): 20% by mass) was used as composition (yb).

[0512] Manufacturing Example 5

[0513] (Preparation of composition (yc))

[0514] In a solution of 100 parts by weight (solid content ratio) of the urethane acrylate resin (II) obtained in Manufacturing Example 3 above, which serves as a non-adhesive resin (y1), 6.3 parts by weight (solid content ratio) of hexamethylene diisocyanate crosslinking agent (manufactured by Tosoh Corporation, product name "Coronate HL") as a crosslinking agent, 1.4 parts by weight (solid content ratio) of dioctyltin bis(2-ethylhexanoate) as a catalyst, and 27.9 parts by weight (solid content ratio) of copper phthalocyanine pigment blue (manufactured by NIKKO BICS Corporation) as a colorant were mixed to obtain a mixture. Then, the mixture was diluted with toluene and stirred until homogeneous to prepare a composition (yc) with a solid content concentration (active ingredient concentration) of 30% by weight.

[0515] Details of the patterned layer support and release material used in the following embodiments and comparative examples are shown below.

[0516] • Support with patterned layer (1): A support with a patterned layer of 5 μm thickness is formed by gravure printing of “opened” text and pattern on the surface of a polyethylene terephthalate film (made by Toray Industries, Inc., with the product name “LUMIRROR (registered trademark)” formed by sanding one side of the film after single-sided pear skin treatment, with a thickness of 38 μm) and drying.

[0517] • Patterned support (2): A patterned support with a thickness of 5 μm is formed on the entire surface of the pear-skin treated side of a polyethylene terephthalate film (made by Toray Industries, Inc., with the product name "LUMIRROR (registered trademark)" formed by treating one side of the film with a single-sided pear-skin treatment with a resin solution containing acrylic resin (an acrylic polymer with methyl methacrylate as the main monomer) and dried.

[0518] • Substrate layer film (1): Biaxially stretched polyester film (manufactured by Mitsubishi Chemical Corporation, product name "DIAFOIL (registered trademark)", polyethylene terephthalate film, thickness: 6μm).

[0519] • Release material: Made by Lindeco Co., Ltd., product name "SP-8LK AO", thickness: 88μm, a material made by polyolefin coating of cellophane and silicone release treatment.

[0520] Example 1

[0521] (1) Formation of coating film

[0522] A coating film (x-1') formed by the composition (x-1) prepared in Manufacturing Example 1 is formed on the patterned layer forming surface of the support (1) with the patterned layer described above. A multilayer die coater (width: 250 mm) is used to simultaneously coat the coating film (x-1') and a coating film (y-a') formed by the composition (ya) prepared in Manufacturing Example 3 is formed on the coating film (x-1'), and a coating film (x-2') formed by the composition (x-2) prepared in Manufacturing Example 2 is formed on the coating film (y-a').

[0523] It should be noted that the coating speed and coating amount of each composition used to form coating film (x-1'), coating film (y-a') and coating film (x-2') are adjusted to achieve the thickness (total thickness) of the adhesive laminate (P1) and the thickness (thickness ratio) of each layer (first adhesive layer (X1), substrate layer (Y), and second adhesive layer (X2)) as described in Table 1.

[0524] (2) Drying treatment

[0525] The formed coatings (x-1'), (y-a'), and (x-2') are simultaneously dried at a drying temperature of 125°C for 60 seconds to form an adhesive laminate (P1) in which the support, pattern layer, first adhesive layer (X1), substrate layer (Y), and second adhesive layer (X2) are directly stacked from the support side.

[0526] Then, the pre-prepared peeling material is laminated onto the surface of the exposed adhesive layer (X2) to obtain the peel detection label 1.

[0527] Examples 2 and 3

[0528] The coating amounts of each composition used to form coatings (x-1'), coatings (y-a'), and coatings (x-2') were adjusted to achieve the thickness (total thickness) of the adhesive laminate (P1) and the thickness (thickness ratio) of each layer (first adhesive layer (X1), substrate layer (Y), and second adhesive layer (X2)) as described in Table 1. Otherwise, peel detection labels 2 and 3 were obtained using the same method as in Example 1.

[0529] Example 4

[0530] Instead of composition (ya), composition (yb) prepared in Manufacturing Example 4 was used. Otherwise, peel detection label 4 was obtained using the same method as in Example 1.

[0531] Example 5

[0532] Instead of composition (ya), composition (yc) prepared in Manufacturing Example 5 was used. Otherwise, peel detection label 5 was obtained using the same method as in Example 1.

[0533] Example 6

[0534] A coating film (x-1') formed by the composition (x-1) prepared in Manufacturing Example 1 is applied to the patterned layer forming surface of the support (1) with the patterned layer using a coater, and then dried at a drying temperature of 110°C for 120 seconds to form an adhesive layer (X1). Then, the substrate layer is laminated onto the exposed surface of the adhesive layer (X1) using the film (1) as the substrate layer (Y).

[0535] In addition, a coating film (x-2') formed by the composition (x-2) prepared in Manufacturing Example 2 was applied to the pre-prepared release material using a coater, and then dried at a drying temperature of 110°C for 120 seconds to form an adhesive layer (X2).

[0536] Then, the exposed surface of the adhesive layer (X2) with the peeling material is attached to the exposed surface of the film (1) of the substrate layer to obtain the peel detection label 6.

[0537] Comparative Example 1

[0538] (1) Formation of coating film

[0539] Using a coater, a coating film (x-2') formed by the composition (x-2) prepared in Manufacturing Example 2 is formed on the surface of the support (1) with the patterned layer that has undergone pear skin treatment, and the coating film (x-2') is formed to the thickness (total thickness) described in Table 1.

[0540] (2) Drying treatment

[0541] The formed coating (x-2') is dried at a drying temperature of 110°C for 120 seconds to form a laminate in which a support, a pattern layer, and an adhesive layer (X) formed by the composition (x-2) are directly stacked from the support side.

[0542] Then, the pre-prepared peeling material is laminated on the surface of the exposed adhesive layer (X) to obtain a peel detection label 7 that does not have an adhesive laminate.

[0543] Comparative Example 2

[0544] Instead of composition (ya), composition (x-2) prepared in manufacturing example 2 was used. Otherwise, peel detection label 8 without a substrate layer (Y) was obtained using the same method as in example 1.

[0545] Comparative Example 3

[0546] A composition (yd) with a solid content concentration (active ingredient concentration) of 30% by mass was prepared by diluting a styrene-isoprene-styrene block copolymer (manufactured by Zeon Corporation, Japan, product name "QUINTAC (registered trademark) 3433N") with toluene and stirring until homogeneous. Except that this composition (yd) was used instead of composition (ya), a peel detection tag 9 was obtained using the same method as in Example 1.

[0547] Comparative Example 4

[0548] Instead of the patterned layer support (1), a patterned layer support (2) was used. Otherwise, the peel detection label 10 was obtained using the same method as in Example 1.

[0549] The thickness (total thickness) of the adhesive laminate, and the thicknesses of the adhesive layer (X1), substrate layer (Y), and adhesive layer (X2) constituting the peel detection labels produced in the examples and comparative examples, were measured according to the aforementioned method. The measurement results are shown in Table 1. Table 1 shows the total thickness and the thickness ratio of each layer.

[0550] [Table 1]

[0551]

[0552] The peel detection tags produced in the examples and comparative examples were used to measure and evaluate various physical properties and characteristics using the methods shown below. The results are shown in Table 2.

[0553] <Evaluation of Pattern Visibility and Residue>

[0554] The peel test labels made in the examples and comparative examples were cut into sizes of 40 mm in length (MD direction) × 25 mm in width (TD direction), and then the peel material on the second adhesive layer (X2) was removed. The resulting material was used as a test sample.

[0555] Using a 2kg rubber roller, the surface of the adhesive layer (X2) of the above-mentioned test sample was pressed against the acrylic coated board (manufactured by PALTEK Co., Ltd., "SPCC-SD Acrylic Coated Single-sided / White", size: length 150mm × width 70mm × thickness 0.4mm) as the substrate by reciprocating the rubber roller once, and then left to stand in the same environment for 24 hours.

[0556] After standing for 24 hours, the label was peeled off by hand at a peel angle of 135°, and the pattern visibility of the peeled label and the presence or absence of residual adhesive on the adhered object were evaluated visually according to the following criteria. Pattern visibility was evaluated according to the following criteria.

[0557] (Evaluation criteria for pattern visibility)

[0558] • A: Of the total area of ​​the surface with the patterned layer, more than 80% of the area shows the pattern.

[0559] •B: Of the total area of ​​the surface with the patterned layer, more than 50% and less than 80% of the area shows the pattern.

[0560] •C: Of the total area of ​​the surface with the patterned layer, more than 30% and less than 50% of the area shows the pattern.

[0561] • D: Of the total area of ​​the surface with the patterned layer, less than 30% of the area shows the pattern.

[0562] •F: No pattern is displayed.

[0563] (Evaluation criteria for residual adhesive)

[0564] • A: Residual adhesive (transfer) that did not occur on the adhered material.

[0565] •F: Residual adhesive (transfer) occurred on the adhered material.

[0566] <Peeling test label adhesion>

[0567] The peel detection labels produced in the examples and comparative examples were cut into sizes of 200mm in length (MD direction) and 25mm in width (TD direction).

[0568] Then, the peeling material on the second adhesive layer (X2) was removed, and an acrylic coated board (manufactured by PALTEK Co., Ltd., "SPCC-SD Acrylic Coated Single-sided / White") was pasted onto the exposed adhesive layer (X2) in an environment of 23°C and 50% RH (relative humidity), and left to stand in the same environment for 24 hours.

[0569] After standing for 24 hours, the adhesive force of the peel test label was determined by the 180° peel method and the tensile speed of 300 mm / min, based on JIS Z0237:2000.

[0570] [Table 2]

[0571]

[0572] As shown in Table 2, it was confirmed that the peel test labels 1-6 obtained in Examples 1-6 have pattern visibility and do not leave adhesive residue on the adhered object. In particular, it was also confirmed that the peel test labels 1-5 obtained in Examples 1-5 have excellent pattern visibility. Furthermore, it was confirmed that the texture of the displayed "opened" text pattern is matte. This can be attributed to the fact that the surface of the support on the side where the pattern layer is formed is treated with a pear-skin finish. Based on this, it can be confirmed that the above pattern is exhibited due to interfacial peeling between the support and the pattern layer, that is, requirement (1) is satisfied.

[0573] On the other hand, the peel test label of Comparative Example 1, which lacks the aforementioned adhesive laminate, resulted in adhesive residue on the adhered object. Furthermore, the peel test label of Comparative Example 2, which lacks a substrate layer (Y) in the aforementioned adhesive laminate, also resulted in adhesive residue on the adhered object. It can be considered that in the cases of the peel test labels of Comparative Examples 1 and 2, the adhesive layer adhering to the adhered object has poor strength, or it cannot follow the deformation of the adhesive layer when the peel test label is peeled off again, causing it to break and thus resulting in adhesive residue.

[0574] In addition, the elastic modulus of the substrate layer in the adhesive laminate of the peel test label in Comparative Example 3 is low, less than 10 MPa. Therefore, the tensile stress generated during the re-peeling of the peel test label will cause the adhesive laminate to break, resulting in the generation of residual adhesive.

[0575] Furthermore, in Comparative Example 4, the peel test label had a pattern layer formed on the entire surface of the support, resulting in interfacial peeling between the support and the pattern layer, leaving adhesive residue on the adhered object side. Therefore, the text performance and adhesive strength were not evaluated. It should be noted that the results of Comparative Example 4 also confirm that the pattern displayed in the above embodiments is due to interfacial peeling between the pattern layer formed on a portion of the support surface and the support.

[0576] Industrial applicability

[0577] The peel detection label of the present invention can be used to detect whether various containers have been opened or not, to identify or verify the presence or absence of peeling or tampering of labels used for various certificates such as passports and product certificates, and is useful as a peel detection label for use in areas where it is required that no adhesive residue be generated on the adhered object.

Claims

1. A peel detection label, comprising a support, a pattern layer and an adhesive laminate sequentially stacked, and satisfying the following requirement (1), wherein the pattern layer is formed on a portion of the surface of the support, and the adhesive laminate has at least an adhesive layer (X) and a substrate layer (Y), wherein, The adhesive laminate is a laminate (P1) formed by sequentially stacking a first adhesive layer (X1), a substrate layer (Y), and a second adhesive layer (X2) starting from the pattern layer side. The elastic modulus of the substrate layer (Y) is above 15 MPa and below 300 MPa. The substrate layer (Y) is a layer formed from a composition (y) comprising a non-adhesive resin (y1), wherein the non-adhesive resin (y1) is selected from one or more of urethane acrylate resins and acid-modified olefin resins. Requirement (1): When the peel detection label is pasted onto the adherend and then peeled off from the adherend, it is possible to visually detect whether the peel detection label has been peeled off from the adherend based on the interface peeling that occurs between the support and the pattern layer.

2. The peel detection label according to claim 1, wherein, The ratio of the thickness (Xt) of the adhesive layer (X) to the thickness (Yt) of the substrate layer (Y) [(Xt) / (Yt)] is 1 / 3 to 3 / 1.

3. The peel detection label according to claim 1 or 2, wherein, The adhesive laminate is a laminate having an adhesive layer (X) on one surface side of a substrate layer (Y), and the substrate layer (Y) is in contact with the surface of the support and the pattern layer.

4. The peel detection label according to claim 1, wherein, The adhesive layer (X1) is in contact with the surface of the support and the pattern layer.

5. The peel detection label according to claim 1 or 2, wherein, The elastic modulus of the first adhesive layer (X1) is 0.05 MPa or more and 0.70 MPa or less.

6. The peel detection label according to claim 1 or 2, wherein, The surface of the support on the side where the pattern layer is formed is a surface treated with a pear-skin finish.

7. The peel detection label according to claim 6, wherein, The pear skin surface treatment is sandblasting.

8. The peel detection label according to claim 1 or 2, wherein, The pattern layer and the adhesive layer (X) contain resins of the same type.

9. The peel detection label according to claim 1 or 2, wherein, The patterned layer is a layer formed from a composition comprising one or more resins selected from acrylic resins, carbamate resins, urethane acrylate resins, and polyester resins. The adhesive layer (X) is a layer formed from a composition (x) containing an adhesive resin, said adhesive resin comprising one or more selected from acrylic resins, urethane resins, urethane acrylate resins and polyester resins.

10. The peel detection tag according to claim 1 or 2, wherein, At least one of the adhesive layer (X) and the substrate layer (Y) is a layer containing a colorant.

Citation Information

Patent Citations

  • Tampering prevention sheet and tampering prevention label

    JP2010281948A

  • Falsification preventive label and method for manufacturing alteration preventive label

    JP2003345255A

  • Member for preventing tampering

    JP2004170776A